A 30,000-year continuous record of glacial history and water balance from Fish Lake, Utah documents the onset, development, and demise of LGM glaciation - M.B. Abbott; D.W. Marchetti; L. Anderson; J.S. Stoner; B.T. Reilly; J.L. Morris; A.R. Brunelle; V.A. Kraklow; M.J. Power; M.S. Finkenbinder; D.J. Larsen; R.G. Hatfield; et al. (Quaternary Science Reviews, 2026)

Latitudinal mixing and movement of eastern school whiting (Sillago flindersi) in south-eastern Australia indicated from otolith trace element chemistry - Karina C. Hall; Kris Cooling; Brendan P. Kelaher; Kyne Krusic-Golub; Stephen G. Morris; Curtis Champion; Renaud Joannes-Boyau (Estuarine, Coastal and Shelf Science, 2026)

Multiple Strains of Trichomonas gallinae are Widespread in Reservoir Hosts and Environmental Resources in UK Farmland - Rebecca C. Thomas; Jenny C. Dunn; Helen Hipperson; Antony J. Morris; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Molecular Ecology, 2026)
Understanding transmission routes of parasites and pathogens is critical for the development of control measures and mitigation of impacts on host populations. Trichomonas gallinae is a widespread parasite in columbids worldwide, and has emerged as a lethal disease in passerines, particularly finches. The postulated transmission route from columbids to passerines via spillover at shared resources has not yet been empirically tested. Here, we screen 363 birds (261 columbids and 102 non‐columbids) in the UK and France for the presence and strain identity of T. gallinae . To quantify potential environmental transmission, we also screened 51 food and water resources common in farmland, at 12 sites over a 2‐year period. We isolated T. gallinae parasites from 79% of columbids, 36% of non‐columbids, and 39% of environmental resources. Prevalence of the Type A strain was more than double in birds sampled at fed sites compared to those at unfed sites. Strain composition was mirrored in columbids, passerines, and shared food and water resources, providing compelling evidence that T. gallinae , especially the Type A strain, is transmitted via these shared resources. T. gallinae was isolated from high density feeding resources (where supplementary food was provided) nearly three times as often as low density resources (natural areas of seed‐providing vegetation), meaning that careful management of supplementary resources has the potential to reduce T. gallinae prevalence in wild bird populations. Further work needs to test practical means of achieving this, but ensuring any supplementary feeding is provided at low density is likely to be critical to reducing parasite transmission.

Caledochytrium aldermanii gen. Et sp. nov.; a new Labyrinthulomycete displaying a novel reproductive strategy - Jane L. Polglase; Peter C. Morris; Stephen W. Feist; Wilfrid J. Mitchell; Fiona Strachan; Kirsty A. Fraser; James R. Iremonger; Elisabeth A. Dyrynda; Alastair R. Lyndon; Lydia A. Brown (Protist, 2026)

Measurement of the Impact of the 8 April 2024 Total Solar Eclipse on Surface Layer Turbulence and Boundary Layer Structure near Bloomington, Indiana - Sean C. C. Bailey; Christina N. Hisle; Tracy L. Knowles; James W. Morris; Ryan D. Nolin; Nicolas E. Pichette-Emmons; Suzanne Weaver Smith (Boundary-Layer Meteorology, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

MicroRNA Preservation and Viability in the Skin of Stranded Marine Mammals - H. Morris; R. M. L. Carrillo; E. A. Lewallen; C. A. Bonin (Marine Mammal Science, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Gait Retraining with Realtime Feedback May Reduce Pain and Improve Function in Runners: A Systematic Review - Michael S. Crowell; Jamie B. Morris; Ryan C. Peterson; Michael P. DiLullo; Shane A. McKeon; Cameron S. Young (Journal of Science in Sport and Exercise, 2026)
Purpose Running-related lower extremity injuries are common and often linked to modifiable biomechanical factors. Gait retraining (GR) using real-time feedback (RTF) has emerged as a potential intervention to alter running biomechanics and reduce pain, but the clinical effectiveness in injured runners has not been determined. The purpose of this study was to evaluate the effectiveness of GR with RTF on lower extremity pain and function in runners. Methods A systematic search of 4 databases identified studies involving runners over age 18 with lower extremity pain who received GR with RTF. Studies were assessed for methodological quality using National Institutes of Health Quality Assessment Tools. Results Nine studies met inclusion criteria. There were 5 level II studies (2 good, 2 fair, 1 poor quality) and 4 level IV studies (1 good, 3 fair quality). Two RCTs found significant reductions in pain between groups. Two RCTs found no between-group differences but did report significant improvements within groups. All RCTs and case series showed within-group pain reductions (Visual Analogue Scale decrease range: 2.2–5.0; Numerical Pain Rating Scale: 2.1–5.9). Improvements in self-reported function (Lower Extremity Functional Scale, Anterior Knee Pain Scale) were observed in all 5 studies that measured functional outcomes. Protocols varied but typically involved 8–10 sessions over 4–6 weeks using verbal, visual, or auditory feedback to promote a non-rearfoot strike and increased step rate. Conclusion Low certainty evidence supports GR with RTF to reduce pain in runners. While within-group improvements often exceeded clinically meaningful thresholds, small sample sizes, heterogeneity, and limited high-quality trials constrained definitive conclusions and did not allow for meta-analysis. Larger, methodologically rigorous studies are needed to optimize and validate GR protocols using RTF.

Explaining state investment in drinking water infrastructure for disadvantaged communities, 1997-2016 - Xi Chen; Jonathan M. Fisk; John C. Morris; Ryan P. Scott (Utilities Policy, 2026)

Corrigendum to “Temperature and precipitation source variability and glacial dynamics in the southwestern United States at Fish Lake, Utah, since late MIS 4” [Quat. Sci. Rev. 379 (2026) 109919] - J.R. Vornlocher; M.D. O'Beirne; A. DePaoli; J.P. Werne; D.W. Marchetti; L. Anderson; A. Brunelle; J.S. Stoner; B.T. Reilly; J.L. Morris; V.A. Kraklow; M.J. Power; et al. (Quaternary Science Reviews, 2026)

Enhancing the therapeutic efficacy of curcumin in topical applications through nanoformulations - Rajesh Sreedharan Nair; Nashiru Billa; Ajay Babu Pazhayattil; Sarath Chandran C.; Mohammed Tahir Ansari; Kai Bin Liew; Andrew P. Morris (Natural Product Research, 2026)

Temperature and precipitation source variability and glacial dynamics in the southwestern United States at Fish Lake, Utah, since late MIS 4 - J.R. Vornlocher; M.D. O'Beirne; A. DePaoli; J.P. Werne; D.W. Marchetti; L. Anderson; A. Brunelle; J.S. Stoner; B.T. Reilly; J.L. Morris; V.A. Kraklow; M.J. Power; et al. (Quaternary Science Reviews, 2026)

Improvement in Maternal Diet Quality Across Pregnancy Is Associated With Lower Gestational Weight Gain in Women With Obesity From the Illinois Kids Development Study - Kelsi A. Morris; Diana C. Pacyga; Susan L. Schantz; Rita S. Strakovsky (Journal of the Academy of Nutrition and Dietetics, 2026)

The importance of activity metabolism in understanding bioenergetics of free ranging snow crab (Chionoecetes opilio) - C. Konecny; D. Cote; J.M. Nicolas; K.Q. Nguyen; C. Morris (Journal of Experimental Marine Biology and Ecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Incorporating climate-driven disturbance shifts in population models reveals non-additive dynamics - Ryan D. O'Connell; Cecil C. Frost; Kevin Gross; William F. Morris (Biological Conservation, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Two contrasting swamp forest succession pathways in central Congo Basin peatlands - Donna Hawthorne; Ian T. Lawson; Greta C. Dargie; Nicholas T. Girkin; Bart Crezee; William Hiles; George E. Biddulph; Yannick E. Bocko; Arnoud Boom; Corneille E.N. Ewango; Yannick Garcin; Pauline Gulliver; et al. (Quaternary Science Reviews, 2025)

The New South Wales nearshore wave tool – an interactive platform integrating high-resolution wave data for enhanced coastal science and management - Thomas B. Doyle; Andrew Bradford; Sean Garber; Raimundo Ibaceta; Bradley D. Morris; Michael A. Kinsela; Timothy C. Ingleton; Iman Jizan; David Taylor; David J. Hanslow; Kym Bilham (Environmental Modelling & Software, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

The co-existence of Microcoleus strains with gene variations in the anatoxin-a biosynthesis cluster can explain the different toxin profiles observed in freshwater benthic mats - Cecilio Valadez-Cano; Adrian Reyes-Prieto; Lindsay Johnston; Yannan Huang; Hannah Morris; Lydia Zamlynny; André M. Comeau; Daniel G. Beach; Rob C. Jamieson; Janice Lawrence (Toxicon, 2025)

Subsurface manifestation of marine heat waves in the southwestern Indian Ocean - Clea B. Welch; Neil Malan; Daneeja Mawren; Tamaryn Morris; Janet Sprintall; Juliet C. Hermes (Ocean Science, 2025)
Marine heat waves (MHWs) are extreme events of prolonged, anomalously warm ocean temperatures. Globally, marine heat waves are increasing in frequency and intensity and are responsible for long-term impacts on marine ecosystems, which have devastating socio-economic consequences. A key gap in our understanding of MHWs is how they manifest in the subsurface. This paper uses satellite sea surface temperature (SST) data and in situ subsurface temperature observations from expendable bathythermographs (XBTs) to investigate the anomalous water temperature characteristics associated with surface-identified MHWs in the southwestern Indian Ocean (SWIO) and how they progress through the water column. We find that (1) regions of high eddy activity in the Mozambique Channel and southeast of Madagascar, where eddy kinetic energy is high and SST variability is low, are primarily characterised by the occurrence of abrupt and intense MHWs and that (2) the frequency, duration and intensity of these events are largely associated with mesoscale activity. In these eddy corridors, surface-detected MHW case studies demonstrate a strong, deep-reaching subsurface temperature anomaly signal with a maximum intensity below the surface. The majority of these MHWs are associated with anticyclonic eddies, which provide a possible mechanism for the deep extent of the surface MHWs. Improving our understanding of the interaction between mesoscale features and subsurface MHW characteristics will benefit the prediction of MHWs and management of the regions' biodiversity.

Effects of recreational disturbance history on female Trinidadian guppies’ responses to chemical predation cues - Alix J. P. Brusseau; Félixe Dumaresq-Synnott; Jade Morris; Abigail C. Nagl; Adam L. Crane; Grant E. Brown (Environmental Biology of Fishes, 2025)

Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Jonathan H. Timperley; Brogan L. Pett; Bility Geninyan; Ari Saputra; Abraham Vincent; Romeo Weah; Benedictus Freeman; Marshall Guahn; Peter M. Hadfield; Morris T. Jah; Tiecanna Jones; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2025)

Turning riprap into reefs: Integrating oyster shells into shoreline armouring - Thea E. Bradford; Chi C. Lo; Juan Carlos Astudillo; Rainbow W.S. Leung; Charlene Lai; Jay J. Minuti; Carmen K.M. Wong; Stephen J. Hawkins; Rebecca L. Morris; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Potassium isotopic compositions and model exposure ages of lunar soils - Kun Wang; Zhen Tian; Megan Broussard; Mason Neuman; Piers Koefoed; Olga Pravdivtseva; Guillaume Avice; Richard V. Morris; Kees C. Welten; Randy L. Korotev; Bradley L. Jolliff (Geochimica et Cosmochimica Acta, 2025)

Geographic constraints on rapid comprehension of tornado warning information - Jason C. Senkbeil; Kathleen Sherman-Morris; S.M. Asger Ali; Cole Vaughn; Bernard Abubakari; Daniella Alaso (Applied Geography, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Salinity Controls on Steel Biocorrosion relevant to the Disposal of High-level Radioactive Waste - M.N. Rose; C. Boothman; S. Shaw; K. Morris; D.L. Engelberg; M.T. Bailey; J.R. Lloyd (Applied Clay Science, 2025)

Attribute recognition: A new method for grouping planetary images by visual characteristics, using the example of Mn-rich rocks in the floor of Gale crater, Mars - Ari Essunfeld; Jade M. Comellas; Reid A. Morris; Patrick J. Gasda; Dorothea Delapp; Diane Oyen; Candice C. Bedford; Benton C. Clark; Erwin Dehouck; Ryan B. Anderson; Ana Lomashvili; Roger C. Wiens; et al. (Icarus, 2025)

Idiosyncratic Recovery Patterns in Coral Reefs of the Maldives Following Climate Disturbance - M. Donati; C. N. Bianchi; C. Morri; M. Montefalcone (Marine Ecology, 2025)
The severe heatwave that occurred in April–May 2016 caused widespread bleaching and mortality in the Maldivian coral reefs. In this study, the main factors that influenced coral recovery were investigated, that is, reef typology and exposure (ocean vs. lagoon) and depth (5 m vs. 10 m). Field surveys were conducted in 2019 and 2021 on 26 Maldivian reefs through photographic samplings. Changes in coral community structure and composition were analysed using the percent cover of the dominant coral families in the Maldives (Acroporidae, Pocilloporidae, and Poritidae) and of a number of benthic categories (encrusting corals, soft‐bodied organisms, abiotic components). Following the climate disturbance, most of the reefs were still dominated by abiotic components (mainly coral rubble and dead corals) after 5 years, although a slight recovery in hard coral cover was registered. Ocean reefs, dominated by massive Poritidae corals, exhibited a higher recovery capacity than lagoon reefs. Lagoon reefs displayed a higher coral mortality and spatial variability in their recovery patterns and in the coral community composition. Encrusting corals and soft‐bodied organisms played a major role in the reef regeneration. The predicted increase in heatwaves frequency due to climate change makes long‐term monitoring mandatory to tackle coral reefs' recovery potential and to evaluate their resilience to global warming. Photographic sampling represents a cost‐effective methodology to monitor coral communities regularly and objectively evaluate changes in the abundance of the main reef components.

Genetic Diversity and Anatoxin Profiles of Freshwater Benthic Cyanobacteria From Nova Scotia (Canada) - Cecilio Valadez‐Cano; Nicolas Tromas; Adrian Reyes‐Prieto; Lindsay Johnston; Yannan Huang; Hannah Morris; Lydia Zamlynny; Daniel G. Beach; Rob C. Jamieson; Janice Lawrence (Environmental Microbiology, 2025)
Some mat‐forming cyanobacteria produce harmful cyanotoxins, yet benthic species remain understudied compared to planktonic counterparts. This study assesses the diversity, distribution and toxin production of mat‐forming cyanobacteria across lentic and lotic systems in Nova Scotia, Canada. We documented greater cyanobacterial species richness in lentic environments, with six dominant species distributed into two major Microcoleus clades, five of which represent putative novel taxa. Two Microcoleus species with the genetic repertoire to produce anatoxins were prevalent. One has been previously reported in Canada, while the second represents a novel species found exclusively in an environment impacted by discharge from a water treatment plant. We observed variability in the gene clusters responsible for the biosynthesis of anatoxin‐a and associated analogues (ATXs), including the discovery of a novel anaG variant with a ~ 1.7 kb insertion in a Microcoleus strain dominating homoanatoxin‐producing mats. This extended anaG , encoding a polyketide synthase with an additional methyltransferase domain, coexists with shorter variants, leading to the production of a mixture of ATXs. These findings highlight the genetic diversity of benthic cyanobacteria in freshwater environments, with Microcoleus as the primary contributor to the production of ATXs in both lentic and lotic systems, underscoring their potential to produce harmful toxins.

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Do Mexican consumers really care about hen welfare? Understanding their attitudes, constraints and willingness to pay for cage-free eggs - Laura X. Estévez-Moreno; Morris Villarroel; Genaro C. Miranda-de la Lama (Food Quality and Preference, 2025)

Elevation Changes in Restored Marshes at Poplar Island, Chesapeake Bay, MD: I. Trends and Drivers of Spatial Variability - Lorie W. Staver; James T. Morris; Jeffrey C. Cornwell; J. Court Stevenson; William Nardin; Philippe Hensel; Michael S. Owens; Amanda Schwark (Estuaries and Coasts, 2024)
Tidal marshes provide numerous ecosystem services, but are threatened by recent increases in global sea level rise (SLR). Marsh restoration and creation are important strategies for mitigating marsh loss, restoring ecosystem services, increasing coastal community resilience, and providing much needed habitat for threatened species. Dredged material resulting from navigation channel maintenance can provide a substrate for these restoration projects. Few studies, however, have addressed the sustainability of these marshes. The Paul S. Sarbanes Ecosystem Restoration Project at Poplar Island, where fine-grained, nutrient-rich dredged material from upper Chesapeake Bay is being used to create > 302 ha of tidal marshes, provides a case study. The low supply of inorganic sediment is counteracted by abundant nutrients, stimulating high rates of organic matter production and elevation change. Using > 10 years of data from 39 surface elevation tables, we found that the mean low marsh rate of elevation change (7.7 ± 3.21 mm year −1 ) was double the mean high marsh rate (3.6 ± 0.47 mm year −1 ) and exceeded the natural reference marsh (3.0 ± 2.28 mm year −1 ) and relative SLR (5.7 mm year −1 ). By stimulating organic matter production, the high nutrient substrate appears to offset the low inorganic sediment inputs in mid-Chesapeake Bay. Spatial variability was correlated with initial elevation, but was also influenced by local factors that may affect sediment redistribution within the marshes.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Mangrove Cover and Extent of Protection Influence Lateral Erosion Control at Hybrid Mangrove Living Shorelines - Sophie C. Y. Chan; Stephen E. Swearer; Rebecca L. Morris (Estuaries and Coasts, 2024)
Erosion poses a significant threat to coastal and estuarine environments worldwide and is further exacerbated by anthropogenic activities and increasing coastal hazards. While conventional engineered structures, such as seawalls and revetments, are commonly employed to protect shorelines from wave impact and erosion, they can also cause detrimental environmental effects. By creating/restoring coastal habitats with engineered structures, hybrid living shorelines offer coastal protection and other co-benefits. Using aerial imagery, we studied the rates of shoreline change before and after living shoreline installation, and between living shorelines and adjacent bare shorelines in three estuaries in New South Wales, Australia. Mangroves had established behind most rock fillets and displayed a trend of increasing canopy cover with fillet age. In the first 3 years since installation, the rates of lateral shoreline change reduced from − 0.20, − 0.16, and − 0.10 m/year to − 0.03, − 0.01, and 0.06 m/year in living shorelines in Hunter, Manning, and Richmond Rivers, respectively. However, when compared to control shorelines, the effectiveness in reducing erosion varied among living shorelines with mean effect sizes of 0.04, − 0.28, and 1.74 across the three estuaries. A more positive rate of shoreline change was associated with an increasing percentage of mangrove canopy area and an increasing length of protected shoreline at wide channels. While hybrid mangrove living shorelines are a promising solution for mitigating erosion and creating habitats at an estuary-wide scale, they may also contribute to downdrift erosion, emphasising the importance of considering site-specific hydrogeomorphology and sediment movement when installing living shorelines.

Institution-Wide Retreats Foster Organizational Learning and Action at a Comprehensive Cancer Center - Benjamin R. Schrank; John A. Fuller; Colleen M. Gallagher; Van K. Morris; Emma B. Holliday; Kelly Merriman; Lynne Nguyen; Lou Weaver; Kelly Nelson; Elizabeth Chiao; Albert C. Koong; Ernest Hawk; et al. (Journal of Cancer Education, 2024)
Providing safe and informed healthcare for sexual and gender minority (SGM) individuals with cancer is stymied by the lack of sexual orientation and gender identity (SOGI) data reliably available in health records and by insufficient training for staff. Approaches that support institutional learning, especially around sensitive topics, are essential for hospitals seeking to improve practices impacting patient safety and research. We engineered annual institutional retreats to identify and unify stakeholders, promote awareness of gaps and needs, identify initiatives, minimize redundant projects, and coordinate efforts that promote improvements in SGM cancer care, education, and research. The 2022 and 2023 retreats employed a 4-h hybrid format allowing virtual and in-person engagement. Retreat organizers facilitated small-group discussions for brainstorming among participants. We performed descriptive statistics from retreat evaluations. The retreats engaged 104 attendees from distinct departments and roles. Participants expressed robust satisfaction, commending the retreat organization and content quality. Notably, the first retreat yielded leadership endorsement and funding for a Quality Improvement pilot to standardize SOGI data collection and clinical staff training. The second retreat provided a platform for updates on focused efforts across the institution and for receiving direction regarding national best practices for SGM care and research. We report the processes and outcomes of institution-wide retreats, which served as a platform for identifying gaps in organizational healthcare practices and research for SGM individuals with cancer. The strategies described herein may be readily scaled at other cancer hospitals seeking to learn and enact system-wide practice changes that support the needs of SGM patients and families.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Development of Quick Response (QR) Training of Tractor Component Identification, Function, Maintenance, and Safety - Melissa A. Rudolph; Shawn G. Ehlers; Glen C. Morris (Journal of Agromedicine, 2024)

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Persistent poverty and incidence-based melanoma mortality in Texas - Karla Madrigal; Lillian Morris; Kehe Zhang; Emelie Nelson; Tiffaney Tran; Marcita Galindez; Zhigang Duan; Adewole S. Adamson; Hui Zhao; Hung Q. Doan; Madison M. Taylor; Cici Bauer; et al. (Cancer Causes & Control, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

The key characteristics of cardiotoxicity for the pervasive pollutant phenanthrene - E. England; J.W. Morris; C. Bussy; J.C. Hancox; H.A. Shiels (Journal of Hazardous Materials, 2024)

Publisher Correction: The protective effect of endurance running against the pro-invasive effects of ageing in breast cancer cells and mesenchymal stem cells in vitro - Marie-Juliet Brown; Matt Nickels; Elizabeth C. Akam; Mhairi A. Morris (In vitro models, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Metal accumulation in salt marsh soils along the East Coast of the United States - Kristen E. Jezycki; Elise Rodriguez; Christopher B. Craft; Scott C. Neubauer; James T. Morris; Steven T. Goldsmith; Peleg Kremer; Nathaniel B. Weston (Science of The Total Environment, 2024)

Efficient sulfide and methane removal in anaerobic secondary effluent using a pilot-scale membrane-aerated biofilm reactor - Mahilet K. Adem; Ian C. Morris; Chungheon Shin; Sebastien H. Tilmans; William A. Mitch; Craig S. Criddle (Chemical Engineering Journal, 2024)

Assessing compounding climate-related stresses and development pathways on the power sector in the central U.S. - Angelo Costa Gurgel; John Reilly; Jennifer Morris; C. Adam Schlosser; Xiang Gao; Mei Yuan; Karen Tapia-Ahumada (Mitigation and Adaptation Strategies for Global Change, 2024)
Future configurations of the power system in the central region of the USA are dependent on relative costs of alternative power generation technologies, energy and environmental policies, and multiple climate-induced stresses. Higher demand in the summer months combined with compounding supply shocks in several power generation technologies can potentially cause a “perfect storm” leading to failure of the power system. Potential future climate stress must be incorporated in investment decisions and energy system planning and operation. We assess how projected future climate impacts on the power system would affect alternative pathways for the electricity sector considering a broad range of generation technologies and changes in demand. We calculate a “potential supply gap” metric for each pathway, system component, and sub-region of the US Heartland due to climate-induced effects on electricity demand and power generation. Potential supply gaps range from 5% in the North Central region under mild changes in climate to 21% in the Lakes-Mid Atlantic region under more severe climate change. We find increases in electricity demand to be more important in determining the size of the potential supply gap than stresses on power generation, while larger shares of renewables in the power system contribute to lower supply gaps. Our results provide a first step toward considering systemic climate impacts that may require changes in managing the grid or on potential additional capacity/reserves that may be needed.

Nonlinear life table response experiment analysis: Decomposing nonlinear and nonadditive population growth responses to changes in environmental drivers - Ryan D. O'Connell; Daniel F. Doak; Carol C. Horvitz; John B. Pascarella; William F. Morris (Ecology Letters, 2024)
Life table response experiments (LTREs) decompose differences in population growth rate between environments into separate contributions from each underlying demographic rate. However, most LTRE analyses make the unrealistic assumption that the relationships between demographic rates and environmental drivers are linear and independent, which may result in diminished accuracy when these assumptions are violated. We extend regression LTREs to incorporate nonlinear (second‐order) terms and compare the accuracy of both approaches for three previously published demographic datasets. We show that the second‐order approach equals or outperforms the linear approach for all three case studies, even when all of the underlying vital rate functions are linear. Nonlinear vital rate responses to driver changes contributed most to population growth rate responses, but life history changes also made substantial contributions. Our results suggest that moving from linear to second‐order LTRE analyses could improve our understanding of population responses to changing environments.

Model analysis of post-fire management and potential reburn fire behavior - Maureen C. Kennedy; Morris C. Johnson; Sarah C. Harrison (Journal of Environmental Management, 2024)

Balancing conflict and opportunity - spatial planning of shellfish and macroalgae culture systems in a heavily trafficked maritime port - Lisa C. Wickliffe; Jonathan A. Jossart; Seth J. Theuerkauf; Brandon M. Jensen; John B. King; Trent Henry; Paula C. Sylvia; James A. Morris; Kenneth L. Riley (Frontiers in Marine Science, 2024)
Ocean-based industries like shipping, aquaculture, and wind energy are growing at an unprecedented rate resulting in challenges related to siting and environmental management. As marine aquaculture and other ocean-based industries continue to expand, robust marine spatial planning analyses that reconcile existing ocean uses and integrate pertinent environmental and planning data are critical for identifying compatible locations. In this study, a series of geospatial analyses were used for aquaculture siting within and around a heavily trafficked and highly utilized maritime port in the San Diego Bay area of California, USA. Using a centralized geodatabase representing key aquaculture planning spatial datasets, recommendations for specific areas for aquaculture were developed based on appropriate environmental conditions for candidate shellfish and algae aquaculture species culture systems. Areas that were known constraints were first identified to determine potentially usable areas for shellfish and macroalgae (i.e., seaweed) aquaculture using an exclusion analysis, a type of multi-criteria decision analysis, to eliminate all areas without compatibility. Within the remaining usable area, we further considered shellfish and macroalgae culture system-specific factors within a ‘culture systems analysis’ to determine where different culture systems have potential for success. This analysis provides a foundation of coastal intelligence for guiding the aquaculture industry and natural resource managers towards appropriate siting decisions. This study can serve as a replicable example of aquaculture spatial planning approaches for siting sustainable aquaculture and other blue economy industries.

Microbial interactions with phosphorus containing glasses representative of vitrified radioactive waste - C.L. Thorpe; R. Crawford; R.J. Hand; J.T. Radford; C.L. Corkhill; C.I. Pearce; J.J. Neeway; A.E. Plymale; A.A. Kruger; K. Morris; C. Boothman; J.R. Lloyd (Journal of Hazardous Materials, 2024)

GOES GLM, biased bolides, and debiased distributions - Anthony Ozerov; Jeffrey C. Smith; Jessie L. Dotson; Randolph S. Longenbaugh; Robert L. Morris (Icarus, 2024)

Perceptions of weather-based pain forecasts and their effect on daily activities - Christopher J. Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Kathleen Sherman-Morris; Andrew E. Mercer (International Journal of Biometeorology, 2024)

Influence of water saturation on interlayer properties of HDTMA-, HDTMP-, and HDPy-modified montmorillonite organoclays - Molly S. Costanza-Robinson; Emory M. Payne; Elaine Dellinger; Kae Fink; Richard C. Bunt; Malcolm Littlefield; Barbara A. Mejaes; Rachael K. Morris; Lauren N. Pincus; Emma H. Wilcox (Applied Clay Science, 2024)

Decentralised solar-based water treatment – Bridging the last mile to water security in low- and middle-income countries? - Brandon Reyneke; Tinta C. Morris; Pilar Fernández-Ibáñez; Kevin G. McGuigan; Ashley Heida; Kerry A. Hamilton; Wesaal Khan (Water Security, 2023)

Un‘covering’ blanket bonds: Assessing the adoption of blanket bonds across the states - Nurun Naher; Adam P. Mayer; Jonathan M. Fisk; John C. Morris (The Extractive Industries and Society, 2023)

Patterns and drivers of early conifer regeneration following stand-replacing wildfire in Pacific Northwest (USA) temperate maritime forests - Madison M. Laughlin; Liliana K. Rangel-Parra; Jenna E. Morris; Daniel C. Donato; Joshua S. Halofsky; Brian J. Harvey (Forest Ecology and Management, 2023)

Characterization of the internal working-life exposome using minimally and non-invasive sampling methods - a narrative review - Eline Verscheure; Rob Stierum; Vivi Schlünssen; Anne Mette Lund Würtz; Dorian Vanneste; Manolis Kogevinas; Barbara N. Harding; Karin Broberg; Shan Zienolddiny-Narui; Johanna Samulin Erdem; Mrinal K. Das; Konstantinos C. Makris; et al. (Environmental Research, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Changing nutritional seascapes of kelp forests - Tanika C. Shalders; Curtis Champion; Kirsten Benkendorff; Tom Davis; Thomas Wernberg; Stephen Morris; Melinda A. Coleman (Frontiers in Marine Science, 2023)
Ocean warming and short-term extreme events (e.g. marine heatwaves) are becoming more intense and frequent and have had major impacts on ecosystems. Seaweeds are foundational components of temperate reefs, providing nutrition for a diversity of species and underpinning temperate food webs. While the impacts of climate-driven environmental change on seaweed distribution, abundance and interactions are well studied, potential impacts on the provision of nutrients from seaweeds and their availability to consumers remain poorly understood. Here, we use metabolomic and lipidomic approaches to understand how the provision of nutrients from key seaweeds may be altered under climate change. We optimize a small-scale microextraction technique to test the effects of warming and marine heatwaves on the nutritional quality of two Australian habitat-forming seaweeds; Ecklonia and Sargassum . We then model changes in lipid availability in response to climate-driven ocean warming throughout Ecklonia ’s eastern Australian distribution. Contrary to expectations, ocean warming and marine heatwaves had limited effects on seaweed nutritional quality, indicating resilience in the nutritional value of these species to climate-driven warming. However, nutritional quality varied significantly between species, which presents new implications for predicted species redistributions from the base of the food chain. Modelling revealed a projected net loss of 3.5% of lipids across the east coast of Australia by 2100 under RCP 8.5 in response to shifts in the redistribution of Ecklonia biomass. The climate-driven redistribution of seaweeds is likely to alter the availability of seaweed-derived nutrients to consumers, which may have broad implications for the transfer of energy within temperate marine food webs.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Ocean acidification influences the gene expression and physiology of two Caribbean bioeroding sponges - John T. Morris; Ian C. Enochs; Michael S. Studivan; Benjamin D. Young; Anderson Mayfield; Nash Soderberg; Nikki Traylor-Knowles; Graham Kolodziej; Derek Manzello (Frontiers in Marine Science, 2023)
Introduction Coral reef ecosystems are experiencing increased rates of carbonate dissolution due to losses in live coral cover coupled with the impacts of ocean acidification (OA) on coral reef calcifiers and bioeroders. While the stimulating effect of OA on bioerosion has been demonstrated experimentally, predominantly in the Pacific, the underlying physiological and molecular mechanisms behind the response are still poorly understood. Methods To address this, we subjected common zooxanthellate ( Cliona varians ) and azooxanthellate ( Pione lampa ) Caribbean sponges to pre-industrial (8.15 pH), present-day (8.05 pH), and two future OA scenarios (moderate OA, 7.85 pH; extreme OA, 7.75 pH) and evaluated their physiological and transcriptomic responses. Results The influence of OA on sponge bioerosion was nonlinear for both species, with the greatest total bioerosion and chemical dissolution rates found in the 7.85 pH treatment, then not increasing further under the more extreme 7.75 pH conditions. A trend towards reduced bioerosion rates in the 7.75 pH treatment occurred regardless of the presence of algal symbionts and suggests that the sponges may become physiologically impaired under prolonged OA exposure, resulting in diminished bioerosion potential. These findings were supported by the RNA-seq analysis, which revealed differentially expressed genes involved in a stress response to OA, in particular, suppressed metabolism. Discussion This may indicate that the sponges had reallocated energy resources towards more critical physiological needs in response to OA as a survival mechanism under stressful conditions. These data reveal that while the bioerosion rates of excavating sponges in Caribbean reef ecosystems may increase under moderate OA scenarios, this OA-stimulation may plateau or be lost at extreme end-of-century pH conditions, with implications for the dissolution and long-term persistence of reef habitat structures.

Fuel Profiles and Biomass Carbon Following Bark Beetle Outbreaks: Insights for Disturbance Interactions from a Historical Silvicultural Experiment - Jenna E. Morris; Michele S. Buonanduci; Michelle C. Agne; Mike A. Battaglia; Daniel C. Donato; Brian J. Harvey (Ecosystems, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The protective effect of endurance running against the pro-invasive effects of ageing in breast cancer cells and mesenchymal stem cells in vitro - Marie-Juliet Brown; Matt Nickels; Elizabeth C. Akam; Mhairi A. Morris (In vitro models, 2023)
Purpose Regular exercise is known to reduce cancer risk and may prevent metastases, however, modelling this in vitro is challenging due the heterogeneity of the tumour microenvironment. Exercised serum can be used to capture changes in cellular signalling components in response to different types and durations of exercise. In this study, exercised serum from long-term endurance runners and sprinters of different ages was used to evaluate the impact of exercise on the invasiveness of breast cancer cells and mesenchymal stem cells in vitro . Methods Exercised serum from long-term trained younger and older endurance runners and sprinters was used to supplement cell culture media in the 3D culture of spheroids containing breast cancer cells or mesenchymal stem cells. Spheroids were generated in a 3D semi-solid matrix and cell invasion was measured using ImageJ software. Statistical analyses of invasion were conducted using one-way ANOVAs. Results Invasion was significantly greater in cells cultured with serum from older, inactive participants compared to young, inactive participants (YC vs OC; F (1,3) = 37.135, P = 0.009). No significant difference was found in the invasion of MDA-MB-231 breast cancer cells cultured in serum from older, long-term endurance runners and younger, long-term endurance runners (YE vs OE; F (1,3) = 5.178, P = 0.107), suggesting a protective effect of endurance running against the pro-invasive effects of ageing. Conclusion This is the first study of its kind to demonstrate the protective effects of long-term exercise training type in two populations of different ages against the invasiveness of breast cancer cells in vitro .

Holocene vegetation dynamics of circum-Arctic permafrost peatlands - Richard E. Fewster; Paul J. Morris; Graeme T. Swindles; Ruza F. Ivanovic; Claire C. Treat; Miriam C. Jones (Quaternary Science Reviews, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Vadose-zone alteration of metaschoepite and ceramic UO2 in Savannah River Site field lysimeters - Connaugh M. Fallon; William R. Bower; Brian A. Powell; Francis R. Livens; Ian C. Lyon; Alana E. McNulty; Kathryn Peruski; J. Frederick W. Mosselmans; Daniel I. Kaplan; Daniel Grolimund; Peter Warnicke; Dario Ferreira-Sanchez; et al. (Science of The Total Environment, 2023)

Behavioural biology of South American domestic camelids: An overview from a welfare perspective - Genaro C. Miranda-de la Lama; Morris Villarroel (Small Ruminant Research, 2023)

Effect of lifestyle-based lipid lowering interventions on the relationship between circulating levels of per-and polyfluoroalkyl substances and serum cholesterol - Stephanie Morgan; M. Abdul Mottaleb; Maria P. Kraemer; Debra K. Moser; Jessica Worley; Andrew J. Morris; Michael C. Petriello (Environmental Toxicology and Pharmacology, 2023)

The Impact of Transcranial Magnetic Stimulation on Reading Processes: A Systematic Review - C. Nikki Arrington; Alexandra E. Ossowski; Humza Baig; Eileen Persichetti; Robin Morris (Neuropsychology Review, 2023)

Attaining freshwater and estuarine-water soil saturation in an ecosystem-scale coastal flooding experiment - A. M. Hopple; K. O. Doro; V. L. Bailey; B. Bond-Lamberty; N. McDowell; K. A. Morris; A. Myers-Pigg; S. C. Pennington; P. Regier; R. Rich; A. Sengupta; R. Smith; et al. (Environmental Monitoring and Assessment, 2023)
Coastal upland forests are facing widespread mortality as sea-level rise accelerates and precipitation and storm regimes change. The loss of coastal forests has significant implications for the coastal carbon cycle; yet, predicting mortality likelihood is difficult due to our limited understanding of disturbance impacts on coastal forests. The manipulative, ecosystem-scale Terrestrial Ecosystem Manipulation to Probe the Effects of Storm Treatments (TEMPEST) experiment addresses the potential for freshwater and estuarine-water disturbance events to alter tree function, species composition, and ecosystem processes in a deciduous coastal forest in MD, USA. The experiment uses a large-unit (2000 m 2 ), un-replicated experimental design, with three 50 m × 40 m plots serving as control, freshwater, and estuarine-water treatments. Transient saturation (5 h) of the entire soil rooting zone (0–30 cm) across a 2000 m 2 coastal forest was attained by delivering 300 m 3 of water through a spatially distributed irrigation network at a rate just above the soil infiltration rate. Our water delivery approach also elevated the water table (typically ~ 2 m belowground) and achieved extensive, low-level inundation (~ 8 cm standing water). A TEMPEST simulation approximated a 15-cm rainfall event and based on historic records, was of comparable intensity to a 10-year storm for the area. This characterization was supported by showing that Hurricane Ida’s (~ 5 cm rainfall) hydrologic impacts were shorter (40% lower duration) and less expansive (80% less coverage) than those generated through experimental manipulation. Future work will apply TEMPEST treatments to evaluate coastal forest resilience to changing hydrologic disturbance regimes and identify conditions that initiate ecosystem state transitions.

Biocircularity: a Framework to Define Sustainable, Circular Bioeconomy - Nicholas M. Holden; Andrew M. Neill; Jane C. Stout; Derek O’Brien; Michael A. Morris (Circular Economy and Sustainability, 2023)
Bioeconomy is proposed as a solution to reduce reliance on fossil resources. However, bioeconomy is not always inherently circular and can mimic the conventional take, make, consume, dispose linear economic model. Agricultural systems will be relied on to provide food, materials, and energy, so unless action is taken, demand for land will inevitably exceed supply. Bioeconomy will have to embrace circularity to enable production of renewable feedstocks in terms of both biomass yield and maintaining essential natural capital. The concept of biocircularity is proposed as an integrated systems approach to the sustainable production of renewable biological materials focusing on extended use, maximum reuse, recycling, and design for degradation from polymers to monomers, while avoiding the “failure” of end of life and minimizing energy demand and waste. Challenges are discussed including sustainable production and consumption; quantifying externalities; decoupling economic growth from depletion; valuing natural ecosystems; design across scales; renewable energy provision; barriers to adoption; and integration with food systems. Biocircularity offers a theoretical basis and measures of success, for implementing sustainable circular bioeconomy.

Rainfall effects on vertical profiles of airborne fungi over a mixed land-use context at the Brazilian Atlantic Forest biodiversity hotspot - Maurício C. Mantoani; Ana P.M. Emygdio; Cristiane Degobbi; Camila Ribeiro Sapucci; Lara C.C. Guerra; Maria A.F.S. Dias; Pedro L.S. Dias; Rafael H.S. Zanetti; Fábio Rodrigues; Gabriel G. Araujo; Dulcilena M.C. Silva; Valter Batista Duo Filho; et al. (Agricultural and Forest Meteorology, 2023)

Hemoglobin normalization outperforms other methods for standardizing dried blood spot metabolomics: A comparative study - Abhishek Jain; Montana Morris; Elizabeth Z. Lin; Sajid A. Khan; Xiaomei Ma; Nicole C. Deziel; Krystal J. Godri Pollitt; Caroline H. Johnson (Science of The Total Environment, 2023)

High-Dose Vitamin C Prevents Secondary Brain Damage After Stroke via Epigenetic Reprogramming of Neuroprotective Genes - Kahlilia C. Morris-Blanco; Anil K. Chokkalla; TaeHee Kim; Saivenkateshkomal Bhatula; Mario J. Bertogliat; Alexis B. Gaillard; Raghu Vemuganti (Translational Stroke Research, 2022)

Local stressors mask the effects of warming in freshwater ecosystems - Olivia F. Morris; Charlie J. G. Loewen; Guy Woodward; Ralf B. Schäfer; Jeremy J. Piggott; Rolf D. Vinebrooke; Michelle C. Jackson (Ecology Letters, 2022)
Climate warming is a ubiquitous stressor in freshwater ecosystems, yet its interactive effects with other stressors are poorly understood. We address this knowledge gap by testing the ability of three contrasting null models to predict the joint impacts of warming and a range of other aquatic stressors using a new database of 296 experimental combinations. Despite concerns that stressors will interact to cause synergisms, we found that net impacts were usually best explained by the effect of the stronger stressor alone (the dominance null model), especially if this stressor was a local disturbance associated with human land use. Prediction accuracy depended on stressor identity and how asymmetric stressors were in the magnitude of their effects. These findings suggest we can effectively predict the impacts of multiple stressors by focusing on the stronger stressor, as habitat alteration, nutrients and contamination often override the biological consequences of higher temperatures in freshwater ecosystems.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Controlling Hydraulic Fracture Growth Through Precise Vertical Placement of Lateral Wells: Insights from HFTS Experiment and Numerical Validation - W. Fu; J. P. Morris; C. S. Sherman; P. Fu; J. Huang (Rock Mechanics and Rock Engineering, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

MicroRNA miR-21 Decreases Post-stroke Brain Damage in Rodents - Mary S. Lopez; Kahlilia C. Morris-Blanco; Nancy Ly; Carly Maves; Robert J. Dempsey; Raghu Vemuganti (Translational Stroke Research, 2022)

Inflammation and Nitro-oxidative Stress as Drivers of Endocannabinoid System Aberrations in Mood Disorders and Schizophrenia - Gerwyn Morris; Luba Sominsky; Kenneth R. Walder; Michael Berk; Wolfgang Marx; André F. Carvalho; Chiara C. Bortolasci; Michael Maes; Basant K. Puri (Molecular Neurobiology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Mapping the Shoreface of Coastal Sediment Compartments to Improve Shoreline Change Forecasts in New South Wales, Australia - M. A. Kinsela; D. J. Hanslow; R. C. Carvalho; M. Linklater; T. C. Ingleton; B. D. Morris; K. M. Allen; M. D. Sutherland; C. D. Woodroffe (Estuaries and Coasts, 2022)
The potential response of shoreface depositional environments to sea level rise over the present century and beyond remains poorly understood. The shoreface is shaped by wave action across a sedimentary seabed and may aggrade or deflate depending on the balance between time-averaged wave energy and the availability and character of sediment, within the context of the inherited geological control. For embayed and accommodation-dominated coastal settings, where shoreline change is particularly sensitive to cross-shore sediment transport, whether the shoreface is a source or sink for coastal sediment during rising sea level may be a crucial determinant of future shoreline change. While simple equilibrium-based models (e.g. the Bruun Rule) are widely used in coastal risk planning practice to predict shoreline change due to sea level rise, the relevance of fundamental model assumptions to the shoreface depositional setting is often overlooked due to limited knowledge about the geomorphology of the nearshore seabed. We present high-resolution mapping of the shoreface-inner shelf in southeastern Australia from airborne lidar and vessel-based multibeam echosounder surveys, which reveals a more complex seabed than was previously known. The mapping data are used to interpret the extent, depositional character and morphodynamic state of the shoreface, by comparing the observed geomorphology to theoretical predictions from wave-driven sediment transport theory. The benefits of high-resolution seabed mapping for improving shoreline change predictions in practice are explored by comparing idealised shoreline change modelling based on our understanding of shoreface geomorphology and morphodynamics before and after the mapping exercise.

Successful storage of Trichomonas gallinae on Whatman FTA cards following culture - Rebecca C. Thomas; Jenny C. Dunn; Chris J. Orsman; Antony J. Morris; Helen Hipperson; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Conservation Genetics Resources, 2022)
Logistical constraints concerning parasite sample storage can hinder progress with the discovery of genetic variation on a global scale. New storage methods are being developed to address this, but require testing in order to understand how widely applicable these methods are. Whatman FTA cards have been tested previously under laboratory conditions for storing low-concentration Trichomonas gallinae isolates with the conclusion that they are not suitable, but have not been tested under field conditions. Here, we conducted a field-test, comparing FTA cards with storage in ethanol for T. gallinae samples collected and cultured from wild Columbiformes in Africa using standard field methods, before transportation to the UK. After 6 months storage, both methods resulted in an overall prevalence of 100% following PCR amplification (n = 59), suggesting that FTA cards are suitable for estimation of T. gallinae prevalence. However, samples stored in ethanol produced more, and longer, sequences than those stored on FTA cards. These data suggest storage in ethanol is preferable for the acquisition of high quality genetic strain data, but that FTA cards can be used successfully to ascertain infection prevalence and identify parasite strains under field conditions.

Assessing rates of parasite coinfection and spatiotemporal strain variation via metabarcoding: Insights for the conservation of European turtle doves Streptopelia turtur - Rebecca C. Thomas; Jenny C. Dunn; Deborah A. Dawson; Helen Hipperson; Gavin J. Horsburgh; Antony J. Morris; Chris Orsman; John Mallord; Philip V. Grice; Keith C. Hamer; Cyril Eraud; Lormée Hervé; et al. (Molecular Ecology, 2022)
Understanding the frequency, spatiotemporal dynamics and impacts of parasite coinfections is fundamental to developing control measures and predicting disease impacts. The European turtle dove ( Streptopelia turtur ) is one of Europe's most threatened bird species. High prevalence of infection by the protozoan parasite Trichomonas gallinae has previously been identified, but the role of this and other coinfecting parasites in turtle dove declines remains unclear. Using a high‐throughput sequencing approach, we identified seven strains of T . gallinae , including two novel strains, from ITS1/5.8S/ITS2 ribosomal sequences in turtle doves on breeding and wintering grounds, with further intrastrain variation and four novel subtypes revealed by the iron‐hydrogenase gene. High spatiotemporal turnover was observed in T . gallinae strain composition, and infection was prevalent in all populations (89%–100%). Coinfection by multiple Trichomonas strains was rarer than expected (1% observed compared to 38.6% expected), suggesting either within‐host competition, or high mortality of coinfected individuals. In contrast, coinfection by multiple haemosporidians was common (43%), as was coinfection by haemosporidians and T . gallinae (90%), with positive associations between strains of T . gallinae and Leucocytozoon suggesting a mechanism such as parasite‐induced immune modulation. We found no evidence for negative associations between coinfections and host body condition. We suggest that longitudinal studies involving the recapture and investigation of infection status of individuals over their lifespan are crucial to understand the epidemiology of coinfections in natural populations.

Geographical variability in the relationship between synoptic weather type and emergency department visits for pain across North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Andrew E. Mercer; Kathleen Sherman-Morris (International Journal of Biometeorology, 2022)

Bioaerosol vertical fungal spores profile in Minas Gerais State, Brazil - Ana Paula Mendes Emygdio; Cristiane Degobbi; Federico Carotenuto; Dulcilena de Matos Castro e Silva; Thaysla Beluco Quintino; Rafael Henrique de Souza Zanetti; Mauricio C. Mantoani; Solana Meneghel Boschilia; Lara Chaves Carvalho Guerra; Pedro Leite da Silva Dias; Cindy E. Morris; Fábio Luiz Teixeira Gonçalves (Aerobiologia, 2022)

Apolipoprotein E ɛ4–related effects on cognition are limited to the Alzheimer’s disease spectrum - Alberto Fernández; Lucía Vaquero; Ricardo Bajo; Pilar Zuluaga; Michael W. Weiner; Andrew J. Saykin; John Q. Trojanowski; Leslie Shaw; Arthur W. Toga; Laurel Beckett; Clifford R. Jack; Paul Aisen; et al. (GeroScience, 2022)
Whether the deleterious effects of APOE4 are restricted to the Alzheimer’s disease (AD) spectrum or cause cognitive impairment irrespectively of the development of AD is still a matter of debate, and the focus of this study. Our analyses included APOE4 genotype, neuropsychological variables, amyloid-βeta (Aβ) and Tau markers, FDG-PET values, and hippocampal volumetry data derived from the healthy controls sample of the ADNI database. We formed 4 groups of equal size ( n = 30) based on APOE4 carriage and amyloid-PET status. Baseline and follow-up (i.e., 48 months post-baseline) results indicated that Aβ-positivity was the most important factor to explain poorer cognitive performance, while APOE4 only exerted a significant effect in Aβ-positive subjects. Additionally, multiple regression analyses evidenced that, within the Aβ-positive sample, hippocampal volumetry explained most of the variability in cognitive performance for APOE4 carriers. These findings represent a strong support for the so-called preclinical/prodromal hypothesis , which states that the reported differences in cognitive performance between healthy carriers and non-carriers are mainly due to the APOE4’s capability to increase the risk of AD. Moreover, our results reinforce the notion that a synergistic interaction of Aβ and APOE4 elicits a neurodegenerative process in the hippocampus that might be the main cause of impaired cognitive performance.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Alternative tissue fixation for combined histopathological and molecular analysis in a clinically representative setting - Amelia Meecham; Elena Miranda; Hayley T. Morris; Jane Hair; Karin A. Oien; Gareth Gerrard; Naomi Guppy; David Mooney; Emily C. Shaw; Margaret Ashton-Key; Robert Lees; Adrienne Flanagan; et al. (Histochemistry and Cell Biology, 2021)
Formalin is the principal tissue fixative used worldwide for clinical and research purposes. Despite optimal preservation of morphology, its preservation of DNA and RNA is poor. As clinical diagnostics increasingly incorporates molecular-based analysis, the requirement for maintaining nucleic acid quality is of increasing importance. Here we assess an alternative non-formalin-based tissue fixation method, PAXgene Tissue system, with the aim of better preserving nucleic acids, while maintaining the quality of the tissue to be used for vital existing diagnostic techniques. In this study, these criteria are assessed in a clinically representative setting. In total, 203 paired PAXgene Tissue and formalin-fixed samples were obtained. Blind-scored haematoxylin and eosin (H&E) sections showed comparable and acceptable staining. Immunohistochemistry (IHC) staining was suboptimal using existing protocols but improved with minor method adjustment and optimisation. Quality of DNA and RNA was significantly improved by PAXgene tissue fixation [RIN 2.8 versus 3.8 ( p < 0.01), DIN 5.68 versus 6.77 ( p < 0.001)], which translated into improved performance on qPCR assay. These results demonstrate the potential of PAXgene Tissue to be used routinely in place of formalin, maintaining adequate histological staining and significantly improving the preservation of biological molecules in the genomic era.

Climatic and landscape changes as drivers of environmental feedback that influence rainfall frequency in the United States - Rachel A. Moore; Davide Martinetti; E. Keith Bigg; Brent C. Christner; Cindy E. Morris (Global Change Biology, 2021)
Previous studies have identified regions where the occurrence of rainfall significantly increases or decreases the probability for subsequent rainfall over periods that range from a few days to several weeks. These observable phenomena are termed “rainfall feedback” (RF). To better understand the land–atmosphere interactions involved in RF, the behavior of RF patterns was analyzed using data from 1849 to 2016 at ~3000 sites in the contiguous United States. We also considered changes in major land‐use types and applied a geographically weighted regression model technique for analyzing the predictors of RF. This approach identified non‐linear and spatially non‐stationary relationships between RF, climate, land use, and land type. RF patterns in certain regions of the United States are predictable by modeling variables associated with climate, season, and land use. The model outputs also demonstrate the extent to which the effect of precipitation, temperature, and land use on RF depend on season and location. Specifically, major changes were observed for land use associated with agriculture in the western United States, which had negative and positive influences on RF in summer and winter, respectively. In contrast, developed land in the eastern United States correlated with positive RF values in summer but with negative ones in winter. We discuss how changes in climate and land use would be expected to affect land–atmosphere interactions, as well as the possible role that physical mechanisms and rain‐enhanced bioaerosol emissions may play in the spatiotemporal changes observed for historical patterns of rainfall frequency in the United States.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Barriers in Implementation of Wastewater Reuse: Identifying the Way Forward in Closing the Loop - J. C. Morris; I. Georgiou; E. Guenther; S. Caucci (Circular Economy and Sustainability, 2021)
The business case for circular economy in water management perspective has gain relevance in the recent times. By 2030, it is estimated that 160% of global total available water will be required to satisfy demand of anthropogenic-related activities and increasing waste-related water will be produced. Gaps on the conceptual framing of water reuse within supply chain management are clearly emerging and the demand for decision support systems helping at assessing effective water consumption in industrial setting is pressing. Despite the numerous local initiatives towards wastewater resource usage, barriers remain for its implementation in practice. Through a systematic review of previous studies in this field, the barriers towards the uptake of wastewater use in agriculture were classified according to the PESTEL (political, economic, social, technological, environmental and legal) framework. Alongside political and legal support, it is identified that for an economically and environmentally sustainable scheme for incentivising the deployment of feasible technologies, there is also a need to gain acceptance for wastewater usage in society in order to enhance the deployment of existing technological solutions. Addressing these factors in tandem can aid the development towards a circular economy for wastewater.

Mangrove growth response to experimental warming is greatest near the range limit in northeast Florida - Samantha K. Chapman; Ilka C. Feller; Gabriela Canas; Matthew A. Hayes; Nicole Dix; Mark Hester; Jim Morris; J. Adam Langley (Ecology, 2021)
Shrubs are invading into grasslands around the world, but we don’t yet know how these shrubs will fare in a warmer future. In ecotonal coastal wetland ecosystems, woody mangroves are encroaching into herbaceous salt marshes owing to changes in temperature, precipitation, and sediment dynamics. Increasing mangrove biomass in wetlands often increases carbon storage, which is high in these productive ecosystems, but little is known about how mangrove growth will change in response to warming. To address this knowledge gap, we deployed warming experiments at three coastal wetland sites along a latitudinal gradient in northeast Florida where Avicennia germinans , black mangroves, are encroaching into salt marshes. We achieved air temperature warming (+1.6°C during the day) at all three sites and measured stem elongation, canopy height and area changes, and leaf and node number. After 2 yr of warming, we found that mangrove growth rate in height increased due to warming. Warming increased stem elongation by 130% over unwarmed control plots after 1 yr at the northern site. Mangrove growth in canopy area did not respond to warming. Site differences in growth rate were pronounced, and mangrove growth in both height and area were lowest at the northern site, despite greater impacts of warming at that site. We also found that area‐based relative growth rate was five times higher across all treatments than height‐based relative growth rate, indicating that mangroves are growing wider rather than taller in these ecotonal environments. Our findings indicate that the growth effect of experimental warming depends on site characteristics and growth parameter measured. We also propose that differential mangrove growth across the three sites may be driven by biotic factors such as the identity of the salt marsh species into which mangroves are encroaching. Our results suggest that, as seen in other ecosystems, wetland plants may respond most strongly to warming at their poleward range edge.

Baclofen attenuates fMRI alcohol cue reactivity in treatment-seeking alcohol dependent individuals - Warren B. Logge; Richard W. Morris; Andrew J. Baillie; Paul S. Haber; Kirsten C. Morley (Psychopharmacology, 2021)

Model Predictions of Postwildfire Woody Fuel Succession and Fire Behavior Are Sensitive to Fuel Dynamics Parameters - Maureen C Kennedy; Morris C Johnson; Sarah C Harrison (Forest Science, 2021)
Computer models used to predict forest and fuels dynamics and wildfire behavior inform decisionmaking in contexts such as postdisturbance management. It is imperative to understand possible uncertainty in model predictions. We evaluated sensitivity of the Fire and Fuels Extension to the Forest Vegetation Simulator predictions to parameters that determine dynamics of standing dead trees (snags) and surface woody fuels. Predicted peak coarse and fine woody fuels were not sensitive to the decomposition rate of snags but were sensitive to decomposition rate of surface fuels regardless of initial snag density. Predictions of coarse woody fuel were sensitive to the snag fall rate when there was a higher initial density of snags. Fire behavior predictions were most sensitive to whether stylized fuel models or modeled fuels were used in calculations. When modeled fuels were used, fire behavior predictions were sensitive to the decomposition rate of surface fuels. Although this analysis does not inform the accuracy of model predictions, it does show where there is potential uncertainty in predictions of woody fuels succession and associated fire behavior. It is likely that any model that predicts postdisturbance fuel succession will also be sensitive to parameters that control snag dynamics and fuel decomposition.

MYCO WELL D-ONE detection of Ureaplasma spp. and Mycoplasma hominis in sexual health patients in Wales - Daniel J. Morris; Lucy C. Jones; Rebecca L. Davies; Kirsty Sands; Edward Portal; Owen B. Spiller (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
The genital mycoplasmas are a unique group of inherently antibiotic-resistant sexually transmitted bacteria, often associated with non-gonococcal urethritis and bacterial vaginosis. The MYCO WELL D-ONE is a culture-based assay that aims to detect these organisms whilst concurrently screening them for antibiotic resistance. Urine and/or swabs from 856 informed and consented participants attending Welsh sexual health clinics were subjected to MYCO WELL D-ONE analysis, alongside qPCR and culture titration methodologies to determine sensitivity, specificity, PPV, NPV and accuracy. Resistance was confirmed by CLSI-compliant susceptibility testing and genetic mechanisms determined. The MYCO WELL D-ONE displayed a sensitivity and specificity of 91.98% and 96.44% for the detection of Ureaplasma spp., with sensitivity and specificity values of 78.23% and 98.84% for Mycoplasma hominis , compared with qPCR. Swabs harboured significantly greater bacterial loads than urine samples for both Ureaplasma spp. and M . hominis . Levofloxacin resistance rates, mediated by Ser83Leu mutation in ParC, for Ureaplasma spp. were 0.54%. Tetracycline resistance rates, mediated by tet (M), were 0.54% and 2% for Ureaplasma spp. and M . hominis , respectively; sequence analysis of tet (M)-positive Ureaplasma spp. and M . hominis strains isolated from a single individual confirmed separate resistance gene origins. The MYCO WELL D-ONE is a sensitive and specific assay for the detection of Ureaplasma spp. and M . hominis in genitourinary medicine samples, facilitating the accurate detection of these organisms within low-technology environments. While good for antibiotic resistance screening, accurate confirmation by MIC determination or molecular methods are required, and more optimally performed on urine samples.

Association between personality and tau-PET binding in cognitively normal older adults - Stephanie A. Schultz; Brian A. Gordon; Shruti Mishra; Yi Su; John C. Morris; Beau M. Ances; Janet M. Duchek; David A. Balota; Tammie L. S. Benzinger (Brain Imaging and Behavior, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Relationship between synoptic weather type and emergency department visits for different types of pain across the Triangle region of North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Andrew E. Mercer; Kathleen Sherman-Morris (International Journal of Biometeorology, 2020)

Microscale Variability in Biomass and Photosynthetic Activity of Microphytobenthos During a Spring-Neap Tidal Cycle - Jacco C. Kromkamp; Ed Morris; Rodney M. Forster (Frontiers in Marine Science, 2020)

An extreme climate transition in the Caribbean's Virgin Islands. II. Sun and Northern hemisphere atmospheric–oceanic feedbacks - N. Brice Orange; Noah Stolz; Molly Ryan; David L. Chesny; Bruce Gendre; Avram G. Primack; Timothy W. Giblin; David C. Morris (International Journal of Climatology, 2020)
The last 60 years of extreme climate variability, and a 1980s climatic shift in the Caribbean's Virgin Islands were analysed to explore relationships with the Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), El‐Niño Southern Oscillation (ENSO), and sunspot numbers. AMO, NAO, ENSO, and sunspot number relationships with the Virgin Islands climate were assessed from measures to their number density of statistically significant correlation with 17 extreme climate indices. Decadal daytime cooling negatively (positively) correlated with AMO (ENSO) records, while moderate nightly warming positively related to the AMO, ENSO, and NAO. In the decades following the late 1970s to early 1980s, evidence was suggestive of an increased lead time for local temperature responses. A relationship with sunspots in extreme temperature was indicated in daytime variations, at a lead time consistent with NAO influences expected from solar activity. The NAO, and to a lesser extent the ENSO, exhibited a negative association to extreme precipitation, while the AMO and sunspot number records only supported a connectivity post 1970s. Twentieth century strengthening of the tropical Atlantic tripole in sea surface temperatures is implicated as the source of decadal warming, and an increasingly rainy climate. More frequent poleward shifts of the Atlantic Intertropical Convergence Zone are suggested to explain recent decadal rises in intense rainfall events, from increased occurrences in organized deep convection.

Coral persistence despite extreme periodic pH fluctuations at a volcanically acidified Caribbean reef - I. C. Enochs; N. Formel; D. Manzello; J. Morris; A. B. Mayfield; A. Boyd; G. Kolodziej; G. Adams; J. Hendee (Coral Reefs, 2020)

Inter-trial phase coherence of visually evoked postural responses in virtual reality - David Engel; Adrian Schütz; Milosz Krala; Jakob C. B. Schwenk; Adam P. Morris; Frank Bremmer (Experimental Brain Research, 2020)
Vision plays a central role in maintaining balance. When humans perceive their body as moving, they trigger counter movements. This results in body sway, which has typically been investigated by measuring the body’s center of pressure (COP). Here, we aimed to induce visually evoked postural responses (VEPR) by simulating self-motion in virtual reality (VR) using a sinusoidally oscillating “moving room” paradigm. Ten healthy subjects participated in the experiment. Stimulation consisted of a 3D-cloud of random dots, presented through a VR headset, which oscillated sinusoidally in the anterior–posterior direction at different frequencies. We used a force platform to measure subjects’ COP over time and quantified the resulting trajectory by wavelet analyses including inter-trial phase coherence (ITPC). Subjects exhibited significant coupling of their COP to the respective stimulus. Even when spectral analysis of postural sway showed only small responses in the expected frequency bands (power), ITPC revealed an almost constant strength of coupling to the stimulus within but also across subjects and presented frequencies. Remarkably, ITPC even revealed a strong phase coupling to stimulation at 1.5 Hz, which exceeds the frequency range that has generally been attributed to the coupling of human postural sway to an oscillatory visual scenery. These findings suggest phase-locking to be an essential feature of visuomotor control.

Applications of Spatial Autocorrelation Analyses for Marine Aquaculture Siting - Jonathan Jossart; Seth J. Theuerkauf; Lisa C. Wickliffe; James A. Morris Jr. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Genetic variances and covariances of live weight traits in Charolais cattle by multi-trait analysis - J. B. Herrera-Ojeda; G. M. Parra-Bracamonte; N. Lopez-Villalobos; J. C. Martínez-González; J. G. Magaña-Monforte; S. T. Morris; L. A. López-Bustamante (Journal of Applied Genetics, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Inhibition of the Epigenetic Regulator REST Ameliorates Ischemic Brain Injury - Kahlilia C. Morris-Blanco; TaeHee Kim; Mario J. Bertogliat; Suresh L. Mehta; Anil K. Chokkalla; Raghu Vemuganti (Molecular Neurobiology, 2019)

Correction to: EUROCAT: an update on its functions and activities - F. D. Tucker; J. K. Morris; A. Neville; E. Garne; A. Kinsner-Ovaskainen; M. Lanzoni; M. A. Loane; S. Martin; C. Nicholl; J. Rankin; A. K. Rissmann (Journal of Community Genetics, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Estimating the birth prevalence and pregnancy outcomes of congenital malformations worldwide - Sowmiya Moorthie; Hannah Blencowe; Matthew W. Darlison; Joy Lawn; Joan K. Morris; Bernadette Modell; A. H. Bittles; H. Blencowe; A. Christianson; S. Cousens; M. W. Darlison; S. Gibbons; et al. (Journal of Community Genetics, 2018)

EUROCAT: an update on its functions and activities - F. D. Tucker; J. K. Morris; A. Neville; E. Garne; A. Kinsner-Ovaskainen; M. Lanzoni; M. A. Loane; S. Martin; C. Nicholl; J. Rankin; A. K. Rissmann (Journal of Community Genetics, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Invasive Lionfish (Pterois volitans/miles) feeding ecology in Biscayne National Park, Florida, USA - Gorka Sancho; Peter R. Kingsley-Smith; James A. Morris; C. Anna Toline; Vanessa McDonough; Sarah M. Doty (Biological Invasions, 2018)

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

The decline of the Turtle Dove: Dietary associations with body condition and competition with other columbids analysed using high‐throughput sequencing - Jenny C. Dunn; Jennifer E. Stockdale; Rosemary J. Moorhouse‐Gann; Alexandra McCubbin; Helen Hipperson; Antony J. Morris; Philip V. Grice; William O. C. Symondson (Molecular Ecology, 2018)
Dietary changes linked to the availability of anthropogenic food resources can have complex implications for species and ecosystems, especially when species are in decline. Here, we use recently developed primers targeting the ITS 2 region of plants to characterize diet from faecal samples of four UK columbids, with particular focus on the European turtle dove ( Streptopelia turtur ), a rapidly declining obligate granivore. We examine dietary overlap between species (potential competition), associations with body condition in turtle doves and spatiotemporal variation in diet. We identified 143 taxonomic units, of which we classified 55% to species, another 34% to genus and the remaining 11% to family. We found significant dietary overlap between all columbid species, with the highest between turtle doves and stock doves ( Columba oenas ), then between turtle doves and woodpigeons ( Columba palumbus ). The lowest overlap was between woodpigeons and collared doves ( Streptopelia decaocto ). We show considerable change in columbid diets compared to previous studies, probably reflecting opportunistic foraging behaviour by columbids within a highly anthropogenically modified landscape, although our data for nonturtle doves should be considered preliminary. Nestling turtle doves in better condition had a higher dietary proportion of taxonomic units from natural arable plant species and a lower proportion of taxonomic units from anthropogenic food resources such as garden bird seed mixes and brassicas. This suggests that breeding ground conservation strategies for turtle doves should include provision of anthropogenic seeds for adults early in the breeding season, coupled with habitat rich in accessible seeds from arable plants once chicks have hatched.

An extreme climate transition in the Caribbean's Virgin Islands. I. Evidence of teleconnection with the 1976/1977 Pacific climate shift - N. Brice Orange; David L. Chesny; Avram G. Primack; Bruce Gendre; Sandra N. Maina; Timothy W. Giblin; David C. Morris (International Journal of Climatology, 2018)
We present the Caribbean's Virgin Islands’ climate variability over the last 60 years from indices of extreme temperature and precipitation, as well as their quantitative support for a recent climatic shift (1983.2 ± 5.5 years). The region's climate indices (defined via time series averages) and trends (defined via linear least squares regression fitting) of extreme temperature and precipitation were cross‐examined from 1952, 1961, 1978, and 1983–2014 to diagnose: the area's climatic extremes; a climatic transition's role in assessing decadal climate anomaly rates; and to provide an analytically independent test of the transition's existence. Analyses relied on the use of varying physical constraints to include weighting from statistical and non‐statistical uncertainties in our climatic outcomes. We report that diurnal warming and enhanced precipitation accompanied each interval, however, non‐negligible deviations existed in comparisons between the same anomalies in any 2 intervals. Our Virgin Islands’ long (1952, 1961–2014) versus short (1978, 1983–2014) climate variation comparisons provide evidence for the manifestation of decadal (or longer) shifts, and thus, biases, in recent Caribbean reports. Our climatic transition's overlap with the renowned 1976/1977 Pacific event insinuates a local Caribbean teleconnection, and contributes to the evidence growing globally for 1980s’ shifts in an abundance of feedback measures of Earth's energy budget.

Assessing soil ecosystem processes – biodiversity relationships in a nature reserve in Central Europe - Tancredi Caruso; Edith C. Hammer; Stefan Hempel; Josef Kohler; E. Kathryn Morris; Stavros D. Veresoglou; Nora Opitz; Jeannine Wehner; Matthias C. Rillig (Plant and Soil, 2018)

Regional variation in Holocene climate quantified from pollen in the Great Plains of North America - Julie L. Commerford; Eric C. Grimm; Christopher J. Morris; Andrea Nurse; Ivanka Stefanova; Kendra K. McLauchlan (International Journal of Climatology, 2018)
The Great Plains experienced extreme fluctuations in precipitation and temperature throughout the Holocene, but these fluctuations have been difficult to quantify systematically across the region. Pollen has long been used as a proxy for reconstructing climate changes, but its power is limited if a region is devoid of modern pollen samples to facilitate comparison with known climate conditions. Here, we present a set of pollen‐climate transfer functions developed using weighted‐averaging partial least squares to reconstruct mean annual precipitation (MAP), mean temperature of the coldest month (MTcold) and mean temperature of the warmest month (MTwarm). At the foundation of these transfer functions is a new set of 141 modern pollen samples that specifically cover the climate space of the Great Plains. These functions quantify the relationship between pollen assemblages and modern climate in this region ( r = 0.928, 0.838 and 0.897 for MAP, MTcold and MTwarm, respectively). We applied these functions to three previously established pollen records taken from lacustrine sites in the region – Fox Lake, MN; Moon Lake, ND; and Kettle Lake, ND – to reconstruct precipitation and temperature at these sites throughout the Holocene. Annual precipitation reconstructed with these transfer functions at Moon Lake and Kettle Lake does not capture a severe, prolonged period of drought during the mid‐Holocene as seen in many other proxy records from these sites and from the region. Reconciliation of these results involves both the autecology of Ambrosia and the inability of any pollen surface samples to capture seasonal and short‐term variability in precipitation. Thus, the transfer functions correctly reconstruct periodic wet summers and a disturbance factor favouring Ambrosia , but miss the effects of reduced winter precipitation and increased frequency of severe drought. The problem revealed here may be more general to biomes with higher frequency disturbance regimes and more weedy species.

Dynamic Meso-Scale Anchorage of GPI-Anchored Receptors in the Plasma Membrane: Prion Protein vs. Thy1 - Yuri L. Nemoto; Roger J. Morris; Hiroko Hijikata; Taka A. Tsunoyama; Akihiro C. E. Shibata; Rinshi S. Kasai; Akihiro Kusumi; Takahiro K. Fujiwara (Cell Biochemistry and Biophysics, 2017)
The central mechanism for the transmission of the prion protein misfolding is the structural conversion of the normal cellular prion protein to the pathogenic misfolded prion protein, by the interaction with misfolded prion protein. This process might be enhanced due to the homo-dimerization/oligomerization of normal prion protein. However, the behaviors of normal prion protein in the plasma membrane have remained largely unknown. Here, using single fluorescent-molecule imaging, we found that both prion protein and Thy1, a control glycosylphosphatidylinositol-anchored protein, exhibited very similar intermittent transient immobilizations lasting for a few seconds within an area of 24.2 and 3.5 nm in diameter in CHO-K1 and hippocampal neurons cultured for 1- and 2-weeks, respectively. Prion protein molecules were immobile during 72% of the time, approximately 1.4× more than Thy1, due to prion protein’s higher immobilization frequency. When mobile, prion protein diffused 1.7× slower than Thy1. Prion protein’s slower diffusion might be caused by its transient interaction with other prion protein molecules, whereas its brief immobilization might be due to temporary association with prion protein clusters. Prion protein molecules might be newly recruited to prion protein clusters all the time, and simultaneously, prion protein molecules in the cluster might be departing continuously. Such dynamic interactions of normal prion protein molecules would strongly enhance the spreading of misfolded prion protein.

Does climate variability influence the demography of wild primates? Evidence from long‐term life‐history data in seven species - Fernando A. Campos; William F. Morris; Susan C. Alberts; Jeanne Altmann; Diane K. Brockman; Marina Cords; Anne Pusey; Tara S. Stoinski; Karen B. Strier; Linda M. Fedigan (Global Change Biology, 2017)
Earth's rapidly changing climate creates a growing need to understand how demographic processes in natural populations are affected by climate variability, particularly among organisms threatened by extinction. Long‐term, large‐scale, and cross‐taxon studies of vital rate variation in relation to climate variability can be particularly valuable because they can reveal environmental drivers that affect multiple species over extensive regions. Few such data exist for animals with slow life histories, particularly in the tropics, where climate variation over large‐scale space is asynchronous. As our closest relatives, nonhuman primates are especially valuable as a resource to understand the roles of climate variability and climate change in human evolutionary history. Here, we provide the first comprehensive investigation of vital rate variation in relation to climate variability among wild primates. We ask whether primates are sensitive to global changes that are universal (e.g., higher temperature, large‐scale climate oscillations) or whether they are more sensitive to global change effects that are local (e.g., more rain in some places), which would complicate predictions of how primates in general will respond to climate change. To address these questions, we use a database of long‐term life‐history data for natural populations of seven primate species that have been studied for 29–52 years to investigate associations between vital rate variation, local climate variability, and global climate oscillations. Associations between vital rates and climate variability varied among species and depended on the time windows considered, highlighting the importance of temporal scale in detection of such effects. We found strong climate signals in the fertility rates of three species. However, survival, which has a greater impact on population growth, was little affected by climate variability. Thus, we found evidence for demographic buffering of life histories, but also evidence of mechanisms by which climate change could affect the fates of wild primates.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Staphylococcus aureus bacteremia in immunosuppressed patients: a multicenter, retrospective cohort study - G. Sasson; A. D. Bai; A. Showler; L. Burry; M. Steinberg; D. R. Ricciuto; T. Fernandes; A. Chiu; S. Raybardhan; M. Science; E. Fernando; A. M. Morris; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Cognitive Effects of Air Pollution Exposures and Potential Mechanistic Underpinnings - J. L. Allen; C. Klocke; K. Morris-Schaffer; K. Conrad; M. Sobolewski; D. A. Cory-Slechta (Current Environmental Health Reports, 2017)

Phenotypic variation in wild‐type substrains of the model cyanobacterium Synechocystis sp. PCC 6803 - J. N. Morris; J. J. Eaton‐Rye; T. C. Summerfield (New Zealand Journal of Botany, 2017)
Genome re‐sequencing has revealed numerous genetic differences between wild‐type substrains of the model cyanobacterium Synechocystis sp. PCC 6803 held in laboratories around the world. These substrains can be divided into the motile PCC‐lineage and non‐motile GT‐lineage, and frequently display unique genetic mutations that result in residue changes in proteins associated with environmental sensing, gene regulation, cellular transport and photosynthesis. However, despite these findings, phenotypic variation between wild‐type substrains does not appear to have been widely reported. In this study, we compared the growth and physiology of three wild‐type substrains of Synechocystis sp. PCC 6803, the GT‐Kazusa substrain (the source of the original genome sequence for this cyanobacterium), the widely studied PCC‐Moscow substrain, and the GT‐O1 substrain, in use in our laboratory. We found similarity between all three substrains in terms of growth rate, oxygen evolution and total chlorophyll levels. Although differences in cell size, whole‐cell absorption and 77 K fluorescence were observed, the wild‐type substrains analysed here are comparable under standard laboratory conditions.

Methylphenidate during early consolidation affects long-term associative memory retrieval depending on baseline catecholamines - Isabella C. Wagner; Mariët van Buuren; Leonore Bovy; Richard G. Morris; Guillén Fernández (Psychopharmacology, 2017)

Motivations of recreational fishers involved in fish habitat management - C. Copeland; E. Baker; J. D. Koehn; S. G. Morris; I. G. Cowx (Fisheries Management and Ecology, 2017)
This study profiled the motivations of recreational fishers involved in habitat management activities in Australia, USA , UK and Ireland. Fishers were surveyed using an online questionnaire. Primary motivations for involvement were social (‘putting something back’) rather than to increase fish numbers or improve fishing experience. Fishers were more likely to participate in habitat management if they were members of a club or organisation or self‐rated their knowledge of various aspects of fish ecology as very good. Most activities undertaken were relatively simple tasks such as picking up litter and contacting government or the media. Fishers that did not take part in habitat management cited lack of time as the principal reason, but organisational issues (lack of contacts, funding and ideas) were also important. There are considerable opportunities for government agencies and recreational fishing organisations to increase the participation of recreational fishers in habitat management as well as their involvement in more complex tasks through targeted programmes providing contact points, ecological information and administrative support.

Clinicians should use likelihood ratios when comparing tests - A. D. Bai; A. Showler; L. Burry; M. Steinberg; G. A. Tomlinson; C. M. Bell; A. M. Morris (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Characterization of Coastal Drift-Cell Sediment Processes Effecting the Restoration of the Southern Lake Michigan Shoreline - Thomas P. Simon; Charles C. Morris; Erin P. Argyilan (Environmental Management, 2016)

Clinical prediction rules in Staphylococcus aureus bacteremia demonstrate the usefulness of reporting likelihood ratios in infectious diseases - A. D. Bai; A. Showler; L. Burry; M. Steinberg; G. A. Tomlinson; C. M. Bell; A. M. Morris (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Pedelecs as a physically active transportation mode - James E. Peterman; Kalee L. Morris; Rodger Kram; William C. Byrnes (European Journal of Applied Physiology, 2016)

A passive seismic approach to estimating the thickness of sedimentary cover on the Nullarbor Plain, Western Australia - A. Scheib; P. Morris; R. Murdie; C. Delle Piane (Australian Journal of Earth Sciences, 2016)

Fine mapping of the rosy apple aphid resistance locus Dp-fl on linkage group 8 of the apple cultivar ‘Florina’ - G. Pagliarani; E. Dapena; M. Miñarro; C. Denancé; Y. Lespinasse; E. Rat-Morris; M. Troggio; C. E. Durel; S. Tartarini (Tree Genetics & Genomes, 2016)

Non-cultured faecal and gastrointestinal seed samples fail to detect Trichomonad infection in clinically and sub-clinically infected columbid birds - Jenny C. Dunn; Jennifer E. Stockdale; Alexandra McCubbin; Rebecca C. Thomas; Simon J. Goodman; Philip V. Grice; Antony J. Morris; Keith C. Hamer; William O. C. Symondson (Conservation Genetics Resources, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

A Framework to Assess Biogeochemical Response to Ecosystem Disturbance Using Nutrient Partitioning Ratios - J. Marty Kranabetter; Kendra K. McLauchlan; Sara K. Enders; Jennifer M. Fraterrigo; Philip E. Higuera; Jesse L. Morris; Edward B. Rastetter; Rebecca Barnes; Brian Buma; Daniel G. Gavin; Laci M. Gerhart; Lindsey Gillson; et al. (Ecosystems, 2016)

Changing Regional Emissions of Airborne Pollutants Reflected in the Chemistry of Snowpacks and Wetfall in the Rocky Mountain Region, USA, 1993–2012 - George P. Ingersoll; Debra C. Miller; Kristi H. Morris; Jill A. McMurray; Garrett Port; Brian S. Caruso (Water, Air, & Soil Pollution, 2016)

Exercise protects against PCB-induced inflammation and associated cardiovascular risk factors - Margaret O. Murphy; Michael C. Petriello; Sung Gu Han; Manjula Sunkara; Andrew J. Morris; Karyn Esser; Bernhard Hennig (Environmental Science and Pollution Research, 2016)

Nasopharyngeal carriage and macrolide resistance in Indigenous children with bronchiectasis randomized to long-term azithromycin or placebo - K. M. Hare; K. Grimwood; A. B. Chang; M. D. Chatfield; P. C. Valery; A. J. Leach; H. C. Smith-Vaughan; P. S. Morris; C. A. Byrnes; P. J. Torzillo; A. C. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Comparison of locus-specific databases for BRCA1 and BRCA2 variants reveals disparity in variant classification within and among databases - Paris J. Vail; Brian Morris; Aric van Kan; Brianna C. Burdett; Kelsey Moyes; Aaron Theisen; Iain D. Kerr; Richard J. Wenstrup; Julie M. Eggington (Journal of Community Genetics, 2015)

Erratum to: Diquat causes caspase-independent cell death in SH-SY5Y cells by production of ROS independently of mitochondria - R. Nisar; P. S. Hanson; L. He; R. W. Taylor; P. G. Blain; C. M. Morris (Archives of Toxicology, 2015)

Diquat causes caspase-independent cell death in SH-SY5Y cells by production of ROS independently of mitochondria - R. Nisar; P. S. Hanson; L. He; R. W. Taylor; P. G. Blain; C. M. Morris (Archives of Toxicology, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition - Eric Allan; Pete Manning; Fabian Alt; Julia Binkenstein; Stefan Blaser; Nico Blüthgen; Stefan Böhm; Fabrice Grassein; Norbert Hölzel; Valentin H. Klaus; Till Kleinebecker; E. Kathryn Morris; et al. (Ecology Letters, 2015)
Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctionality measures in which ecosystem services were weighted according to realistic land‐use objectives. We found that indirect land‐use effects, i.e. those mediated by biodiversity loss and by changes to functional composition, were as strong as direct effects on average. Their strength varied with land‐use objectives and regional context. Biodiversity loss explained indirect effects in a region of intermediate productivity and was most damaging when land‐use objectives favoured supporting and cultural services. In contrast, functional composition shifts, towards fast‐growing plant species, strongly increased provisioning services in more inherently unproductive grasslands.

Buried Wood: A Common Yet Poorly Documented Form of Deadwood - M. T. Moroni; D. M. Morris; C. Shaw; J. N. Stokland; M. E. Harmon; N. J. Fenton; K. Merganičová; J. Merganič; K. Okabe; U. Hagemann (Ecosystems, 2015)

From Red Tides to Green and Brown Tides: Bloom Dynamics in a Restricted Subtropical Lagoon Under Shifting Climatic Conditions - Edward J. Phlips; Susan Badylak; Margaret A. Lasi; Robert Chamberlain; Whitney C. Green; Lauren M. Hall; Jane A. Hart; Jean C. Lockwood; Janice D. Miller; Lori J. Morris; Joel S. Steward (Estuaries and Coasts, 2015)

Smoking-associated risks of conventional adenomas and serrated polyps in the colorectum - Jane C. Figueiredo; Seth D. Crockett; Dale C. Snover; Carolyn B. Morris; Gail McKeown-Eyssen; Robert S. Sandler; Dennis J. Ahnen; Douglas J. Robertson; Carol A. Burke; Robert S. Bresalier; James M. Church; Timothy R. Church; et al. (Cancer Causes & Control, 2015)

The effect of the weather on pulmonary exacerbations and viral infections among adults with cystic fibrosis - W. G. Flight; R. J. Bright-Thomas; C. Sarran; K. J. Mutton; J. Morris; A. K. Webb; A. M. Jones (International Journal of Biometeorology, 2014)

Relationships among varying sampling distance and the IBI in warmwater, headwater streams of the Eastern Corn Belt Plain - Thomas P. Simon; Charles C. Morris (Environmental Monitoring and Assessment, 2014)

Introduction to Selected Contributions from the 47th US Rock Mechanics/Geomechanics Symposium Held in San Francisco, California from June 23–26, 2013 - Alvin C. Chan; Joseph P. Morris; Laura J. Pyrak-Nolte (Rock Mechanics and Rock Engineering, 2014)

The P seudomonas viridiflava phylogroups in the P . syringae species complex are characterized by genetic variability and phenotypic plasticity of pathogenicity‐related traits - Claudia Bartoli; Odile Berge; Caroline L. Monteil; Caroline Guilbaud; Giorgio M. Balestra; Leonardo Varvaro; Corbin Jones; Jeffery L. Dangl; David A. Baltrus; David C. Sands; Cindy E. Morris (Environmental Microbiology, 2014)
Summary As a species complex, P seudomonas syringae exists in both agriculture and natural aquatic habitats. P . viridiflava , a member of this complex, has been reported to be phenotypically largely homogenous. We characterized strains from different habitats, selected based on their genetic similarity to previously described P . viridiflava strains. We revealed two distinct phylogroups and two different kinds of variability in phenotypic traits and genomic content. The strains exhibited phase variation in phenotypes including pathogenicity and soft rot on potato. We showed that the presence of two configurations of the Type III Secretion System [single ( S ‐ PAI ) and tripartite ( T ‐ PAI ) pathogenicity islands] are not correlated with pathogenicity or with the capacity to induce soft rot in contrast to previous reports. The presence/absence of the avrE effector gene was the only trait we found to be correlated with pathogenicity of P . viridiflava . Other Type III secretion effector genes were not correlated with pathogenicity. A genomic region resembling an exchangeable effector locus ( EEL ) was found in S ‐ PAI strains, and a probable recombination between the two PAIs is described. The ensemble of the variability observed in these phylogroups of P . syringae likely contributes to their adaptability to alternating opportunities for pathogenicity or saprophytic survival.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Cenozoic detrital iron deposits of the Hamersley Province, Western Australia - M. Kneeshaw; R. C. Morris (Australian Journal of Earth Sciences, 2014)

Supply chain and marketing of sea grapes, Caulerpa racemosa (Forsskål) J. Agardh (Chlorophyta: Caulerpaceae) in Fiji, Samoa and Tonga - C. Morris; S. Bala; G. R. South; J. Lako; M. Lober; T. Simos (Journal of Applied Phycology, 2014)

The native production of the sesquiterpene isopterocarpolone by Streptomyces sp. RM-14-6 - Khaled A. Shaaban; Shanteri Singh; Sherif I. Elshahawi; Xiachang Wang; Larissa V. Ponomareva; Manjula Sunkara; Gregory C. Copley; James C. Hower; Andrew J. Morris; Madan K. Kharel; Jon S. Thorson (Natural Product Research, 2014)

Climate change and Mediterranean seagrass meadows: a synopsis for environmental managers - G. PERGENT; H. BAZAIRI; C. N. BIANCHI; C. F. BOUDOURESQUE; M. C. BUIA; S. CALVO; P. CLABAUT; M. HARMELIN-VIVIEN; M. A. MATEO; M. MONTEFALCONE; C. MORRI; S. ORFANIDIS; et al. (Mediterranean Marine Science, 2014)
This synopsis focuses on the effects of climate change on Mediterranean seagrasses, and associated communities, and on the contribution of the main species, Posidonia oceanica, to the mitigation of climate change effects through its role of sequestering carbon dioxide. Whilst the regression of seagrass meadows is well documented, generally linked to anthropogenic pressures, global warming could be a cause of new significant regressions, notably linked to the introduction of exotic species, the rise of Sea-Surface Temperature (SST), and relative sea level. Seagrass communities could also be affected by climate change through the replacement of seagrass species having high structural complexity by species of lower complexity and even by opportunistic introduced species. Although it is currently very difficult to predict the consequences of these alterations and their cascade effects, two main conflicting trends in the functioning of seagrass ecosystems that could occur are acceleration of the herbivore pathway or of the detritivore pathway. The mean net primary production of the dominant species, Posidonia oceanica, is relatively high and can be estimated to range between 92.5 to 144.7 g C m-2 a-1. Around 27% of the total carbon fixed by this species enters the sedimentary pathway leading to formation, over millennia, of highly organic deposits rich in refractory carbon. At the Mediterranean scale, the sequestration rate might reach 1.09 Tg C a-1. The amount of this stored carbon is estimated to range from 71 to 273 kg C m-2, which when considered at the Mediterranean scale would represent 11 to 42% of the CO2 emissions produced by Mediterranean countries since the beginning of the Industrial Revolution. The greatest value of the P. oceanica ecosystem, in the context of mitigation of global climate change, is linked to this vast long-term carbon stock accumulated over the millennia, and therefore, efforts should be focused on preserving the meadows to keep this reservoir intact.

Thirty years after - dramatic change in the coastal marine habitats of Kos Island (Greece), 1981-2013. - C. N. BIANCHI; M. CORSINI-FOKA; C. MORRI; A. ZENETOS (Mediterranean Marine Science, 2014)
Results of recent fieldwork were compared with data collected in 1981, taken as a reference condition. Surveys were conducted with the same method (time-based visual census along random paths), in the same sites, by the same people. Semi-quantitative inventories of conspicuous species were analysed by univariate and multivariate techniques. Available information on the main potential stressors indicated that a regime shift has occurred in these 30+ years: sea surface temperature rose by1-2°C, human pressure grew impressively, and invasion by several alien species took place. Consistently, a phase shift occurred in the biological communities. Of the 120 conspicuous species found in total, only 51 were common to both surveys; 31 species (‘losses’) were found in 1981 but not again in 2013, 38 (‘gains’) were found exclusively in 2013, 16 (‘winners’) increased their abundance, 8 (‘losers’) got scarcer, and 27 underwent little or no change. Gains included 7 alien, 2 nitrophilic, and 7 thermophilic species. Multivariate analysis evidenced biotic homogenisation in 2013 and huge change in rocky reef habitats. The once flourishing algal forests have disappeared to leave space to sponges and wide areas of bare substratum. This has most probably been the result of overgrazing by alien herbivorous fishes (Siganus luridus and S. rivulatus), whose establishment and spread has been favoured by seawater warming; the synergic action of local human impacts was also evidenced.

Bioprecipitation: a feedback cycle linking Earth history, ecosystem dynamics and land use through biological ice nucleators in the atmosphere - Cindy E. Morris; Franz Conen; J. Alex Huffman; Vaughan Phillips; Ulrich Pöschl; David C. Sands (Global Change Biology, 2014)
Landscapes influence precipitation via the water vapor and energy fluxes they generate. Biologically active landscapes also generate aerosols containing microorganisms, some being capable of catalyzing ice formation and crystal growth in clouds at temperatures near 0 °C. The resulting precipitation is beneficial for the growth of plants and microorganisms. Mounting evidence from observations and numerical simulations support the plausibility of a bioprecipitation feedback cycle involving vegetated landscapes and the microorganisms they host. Furthermore, the evolutionary history of ice nucleation‐active bacteria such as Pseudomonas syringae supports that they have been part of this process on geological time scales since the emergence of land plants. Elucidation of bioprecipitation feedbacks involving landscapes and their microflora could contribute to appraising the impact that modified landscapes have on regional weather and biodiversity, and to avoiding inadvertent, negative consequences of landscape management.

Multiple factors influence the role of arbuscular mycorrhizal fungi in soil aggregation—a meta-analysis - Eva F. Leifheit; Stavros D. Veresoglou; Anika Lehmann; E. Kathryn Morris; Matthias C. Rillig (Plant and Soil, 2014)

Spatial models to support the management of coastal marine ecosystems: a short review of the best practices in Liguria, Italy - M. VACCHI; M. MONTEFALCONE; V. PARRAVICINI; A. ROVERE; P. VASSALLO; M. FERRARI; C. MORRI; C. N. BIANCHI (Mediterranean Marine Science, 2013)
Spatial modelling is an emerging approach to the management of coastal marine habitats, as it helps understanding and predicting the results of global change. This paper reviews critically two recent examples developed in Liguria, an administrative region of NW Italy. The first example, aiming at predicting habitat status depending on pressures, provides managers with the opportunity of envisaging different scenarios for the consequences of coastal development choices. The second example defines the status of an important Mediterranean coastal marine habitat (Posidonia oceanica meadows) under natural conditions, allowing for quantifying human impacts on regressed meadows. Both modelling approaches are useful to define the targets of coastal management, and may help choosing the best management option. Well-planned and sustained monitoring is essential to model validation and improvement.

Land use and host neighbor identity effects on arbuscular mycorrhizal fungal community composition in focal plant rhizosphere - E. Kathryn Morris; Francois Buscot; Christine Herbst; Torsten Meiners; Elisabeth Obermaier; Nicole W. Wäschke; Tesfaye Wubet; Matthias C. Rillig (Biodiversity and Conservation, 2013)

Patterns in Stream Fish Assemblage Structure and Function Associated With a PCB Gradient - Thomas P. Simon; Charles C. Morris; Daniel W. Sparks (Archives of Environmental Contamination and Toxicology, 2013)

Flowering of the seagrass Posidonia oceanica in NW Mediterranean: is there a link with solar activity? - M. MONTEFALCONE; E. GIOVANNETTI; C. MORRI; A. PEIRANO; C. N. BIANCHI (Mediterranean Marine Science, 2013)
Time series on the leaf biometry and rhizome production of the endemic Mediterranean seagrass Posidonia oceanica (L.) Delile were investigated in a meadow of the Ligurian Sea (NW Mediterranean) in order to assess changes in the plant growth during a massive flowering event occurred in 2003, in coincidence with the warmest summer temperatures recorded in the last centuries. P. oceanica exhibited the highest values of leaf surface area during the flowering year and the highest values of rhizome production in the previous year. The years immediately following the flowering event were characterized by a decrease in both parameters. Comparison of the years of massive flowering events reported in the literature at the whole Mediterranean-wide spatial scale with the historical series (spanning the last 50 years) of the air temperature and of the sunspot number suggested that intense solar activity, and not warmer temperature per se, was likely to be the main trigger of massive flowering events in Posidonia oceanica.

Assessment of the significance of respiratory culture of Aspergillus in the non-neutropenic patient. A critique of published diagnostic criteria - R. C. Barton; R. P. Hobson; H. McLoughlin; A. Morris; B. Datta (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

A mutation in the start codon of γ-crystallin D leads to nuclear cataracts in the Dahl SS/Jr-Ctr strain - Ashley C. Johnson; Jonathan W. Lee; Ashlyn C. Harmon; Zaliya Morris; Xuexiang Wang; Jonathan Fratkin; John P. Rapp; Elise Gomez-Sanchez; Michael R. Garrett (Mammalian Genome, 2013)

Multiscale assessment of green leaf cover in a semi-arid rangeland with a small unmanned aerial vehicle - Kenneth C. McGwire; Mark A. Weltz; Julie A. Finzel; Christopher E. Morris; Lynn F. Fenstermaker; David S. McGraw (International Journal of Remote Sensing, 2013)

The use of stress‐70 proteins in physiology: a re‐appraisal - J. P. Morris; S. Thatje; C. Hauton (Molecular Ecology, 2013)
There are few factors more important to the mechanisms of evolution than stress. The stress response has formed as a result of natural selection, improving the capacity of organisms to withstand situations that require action. The ubiquity of the cellular stress response suggests that effective mechanisms to counteract stress emerged early in the history of life, and their commonality proves how vital such mechanisms are to operative evolution. The cellular stress response ( CSR ) has been identified as a characteristic of cells in all three domains of life and consists of a core 44 proteins that are structurally highly conserved and that have been termed the ‘minimal stress proteome’ ( MSP ). Within the MSP , the most intensely researched proteins are a family of heat‐shock proteins known as HSP 70. Superficially, correlations between the induction of stress and HSP 70 differential expression support the use of HSP 70 expression as a nonspecific biomarker of stress. However, we argue that too often authors have failed to question exactly what HSP 70 differential expression signifies. Herein, we argue that HSP 70 up‐regulation in response to stressors has been shown to be far more complex than the commonly accepted quasi‐linear relationship. In addition, in many instances, the uncertain identity and function of heat‐shock proteins and heat‐shock cognates has led to difficulties in interpretation of reports of inducible heat‐shock proteins and constitutive heat‐shock cognates. We caution against the broad application of HSP 70 as a biomarker of stress in isolation and conclude that the application of HSP 70 as a meaningful index of stress requires a higher degree of validation than the majority of research currently undertakes.

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

Reply to D. F. Lascelles. Discussion on ‘Microplaty hematite—its varied nature and genesis’ by R. C. Morris and ‘Genesis modelling for the Hamersley BIF-hosted iron ores of Western Australia: a critical review’ by R. C. Morris and M. Kneeshaw - R. C. Morris; M. Kneeshaw (Australian Journal of Earth Sciences, 2012)

Effects of long-term isolation on genetic variation and within-island population genetic structure in Christmas Island (Indian Ocean) seabirds - James A. Morris-Pocock; Janos C. Hennicke; Vicki L. Friesen (Conservation Genetics, 2012)

A summary of pine straw yields and economic benefits in loblolly, longleaf and slash pine stands - E. David Dickens; David J. Moorhead; Charles T. Bargeron; Lawrence A. Morris; Lee A. Ogden; Bryan C. McElvany (Agroforestry Systems, 2012)

Kinetic and phylogenetic analysis of plant polyamine uptake transporters - Vaishali Mulangi; Marcus C. Chibucos; Vipaporn Phuntumart; Paul F. Morris (Planta, 2012)

The effects of energy drink in combination with alcohol on performance and subjective awareness - Chris Alford; Jennifer Hamilton-Morris; Joris C. Verster (Psychopharmacology, 2012)
Rationale This study investigated the coadministration of an energy drink with alcohol to study the effects on subjective intoxication and objective performance. Objectives This study aims to evaluate the objective and subjective effects of alcohol versus placebo at two alcohol doses, alone and in combination with an energy drink, in a balanced order, placebo-controlled, double-blind design. Methods Two groups of ten healthy volunteers, mean (SD) age of 24 (6.5), participated in the study. One group consumed energy drink containing 80 mg of caffeine and the other consumed a placebo drink, with both receiving two alcohol doses (0.046 and 0.087% breathalyser alcohol concentration). Tests included breath alcohol assessment, objective measures of performance (reaction time, word memory and Stroop task) and subjective visual analogue mood scales. Results Participants showed significantly impaired reaction time and memory after alcohol compared to the no alcohol condition and had poorer memory after the higher alcohol dose. Stroop performance was improved with the energy drink plus alcohol combination compared to the placebo drink plus alcohol combination. Participants felt significant subjective dose-related impairment after alcohol compared to no alcohol. Neither breath alcohol concentration nor the subjective measures showed a significant difference between the energy drink and the placebo energy drink when combined with alcohol. Conclusions Subjective effects reflected awareness of alcohol intoxication and sensitivity to increasing alcohol dose. There were no overall significant group differences for subjective measures between energy drink and placebo groups in the presence of alcohol and no evidence that the energy drink masked the subjective effects of alcohol at either dose.

Response to Dr Alan Goode's ‘Discussion’ of Morris & Kneeshaw (2011) - R. C. Morris; M. Kneeshaw (Australian Journal of Earth Sciences, 2012)

Microplaty hematite—its varied nature and genesis - R. C. Morris (Australian Journal of Earth Sciences, 2012)

Chromosomes 3B and 4D are associated with several milling and baking quality traits in a soft white spring wheat (Triticum aestivum L.) population - A. H. Carter; K. Garland-Campbell; C. F. Morris; K. K. Kidwell (Theoretical and Applied Genetics, 2012)

Immunogenetic Management Software: a new tool for visualization and analysis of complex immunogenetic datasets - Z. P. Johnson; R. D. Eady; S. F. Ahmad; S. Agravat; T. Morris; J. Else; S. M. Lank; R. W. Wiseman; D. H. O’Connor; M. C. T. Penedo; C. P. Larsen; L. S. Kean (Immunogenetics, 2012)

Effects of double transport and season on sensorial aspects of lamb's meat quality in dry climates - Genaro C. Miranda-de la Lama; Morris Villarroel; María del Mar Campo; José Luis Olleta; Carlos Sañudo; Gustavo A. María (Tropical Animal Health and Production, 2012)

The genome sequence of Desulfatibacillum alkenivorans AK‐01: a blueprint for anaerobic alkane oxidation - A. V. Callaghan; B. E. L. Morris; I. A. C. Pereira; M. J. McInerney; R. N. Austin; J. T. Groves; J. J. Kukor; J. M. Suflita; L. Y. Young; G. J. Zylstra; B. Wawrik (Environmental Microbiology, 2012)
Summary Desulfatibacillum alkenivorans AK‐01 serves as a model organism for anaerobic alkane biodegradation because of its distinctive biochemistry and metabolic versatility. The D. alkenivorans genome provides a blueprint for understanding the genetic systems involved in alkane metabolism including substrate activation, CoA ligation, carbon‐skeleton rearrangement and decarboxylation. Genomic analysis suggested a route to regenerate the fumarate needed for alkane activation via methylmalonyl‐CoA and predicted the capability for syntrophic alkane metabolism, which was experimentally verified. Pathways involved in the oxidation of alkanes, alcohols, organic acids and n ‐saturated fatty acids coupled to sulfate reduction and the ability to grow chemolithoautotrophically were predicted. A complement of genes for motility and oxygen detoxification suggests that D. alkenivorans may be physiologically adapted to a wide range of environmental conditions. The D. alkenivorans genome serves as a platform for further study of anaerobic, hydrocarbon‐oxidizing microorganisms and their roles in bioremediation, energy recovery and global carbon cycling.

Errata to the Review Article (Medit. Mar. Sci. 11/2, 2010, 381-493): "Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution" - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2011)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia - K. Marrin; B. Drust; W. Gregson; C. J. Morris; N. Chester; G. Atkinson (European Journal of Applied Physiology, 2011)

MercNet: a national monitoring network to assess responses to changing mercury emissions in the United States - David Schmeltz; David C. Evers; Charles T. Driscoll; Richard Artz; Mark Cohen; David Gay; Richard Haeuber; David P. Krabbenhoft; Robert Mason; Kristi Morris; James G. Wiener (Ecotoxicology, 2011)

Genesis modelling for the Hamersley BIF-hosted iron ores of Western Australia: a critical review - R. C. Morris; M. Kneeshaw (Australian Journal of Earth Sciences, 2011)

Divergent effects of two different doses of intranasal oxytocin on facial affect discrimination in schizophrenic patients with and without polydipsia - Morris B. Goldman; Alexandrina M. Gomes; C. S. Carter; Royce Lee (Psychopharmacology, 2011)

Effects of road type during transport on lamb welfare and meat quality in dry hot climates - Genaro C. Miranda-de la Lama; Paula Monge; Morris Villarroel; Jose Luis Olleta; Sylvia García-Belenguer; Gustavo A. María (Tropical Animal Health and Production, 2011)

Investigating the Utilization of Potassium Fertilizer in a Pinus patula Schiede Ex Schltdl. & Cham. Plantation - Jacob W. Crous; Andrew R. Morris; Mary C. Scholes (Forest Science, 2011)
Previous research indicated that the application of phosphorus (P) and potassium (K) fertilizer to Mexican weeping pine (Pinus patula Schiede ex Schltdl. & Cham.) on gabbro-derived soils was necessary to correct a second rotation yield decline. To plan efficient fertilization of subsequent rotations, the fate and utilization of the applied K fertilizer was investigated using the rubidium (Rb)/K reverse tracer technique whereby the naturally occurring Rb in the soil was used as an indicator of native soil K. At the age of 15 years, samples from the soil, forest floor, bark, wood and live foliage were collected from a trial in which various amounts of P and K fertilizer were applied at different stages of stand development. No significant quantity of the applied K remained in the soil at the end of the 15-year rotation, but sufficient plant-available P remained on plots where 80 kg ha−1 P and K was applied. Significantly greater quantities of P per ha were found in the forest floor, wood, and foliage on the plots that received 40 or 80 kg ha−1 P and K compared with the control. The application of 80 kg ha−1 P and K increased the P content of the wood and foliage over that recorded in the 40 kg ha−1 P and K treatment. The application of 80 kg ha−1 P and K increased the K content of the forest floor and foliage compared with that of the control. Across all PK quantities, fertilizer K contributed 28, 17, and 8% to the quantity of K in the wood, bark, and foliage, respectively. The export of up to 52 kg K ha−1 from the site in wood and bark will necessitate the reapplication of at least 104 kg K ha−1 to the subsequent rotation to produce timber sustainably on the gabbro-derived soils at Usutu.

Quality calls: phylogeny and biogeography of a new genus of neotropical katydid (Orthoptera: Tettigoniidae) with ultra pure-tone ultrasonics - FERNANDO MONTEALEGRE-Z; GLENN K. MORRIS; FABIO A. SARRIA-S; ANDREW C. MASON (Systematics and Biodiversity, 2011)

Changes in topsoil, standing litter and tree nutrient content of a Pinus patula plantation after phosphorus and potassium fertilization - J. W. Crous; A. R. Morris; M. C. Scholes (European Journal of Forest Research, 2011)

A comparison of two microbial detection methods used in aseptic processing of musculoskeletal allograft tissues - Jeremy A. Dennis; Octavio V. Martinez; David C. Landy; Theodore I. Malinin; Paul R. Morris; William P. Fox; Billy E. Buck; H. Thomas Temple (Cell and Tissue Banking, 2011)

Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E. GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2010)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

Ecosystem considerations of the KwaZulu-Natal sardine run - L Hutchings; T Morris; C D van der Lingen; S J Lamberth; A D Connell; S Taljaard; L van Niekerk (African Journal of Marine Science, 2010)

The perceived landfall location of evacuees from Hurricane Gustav - J. C. Senkbeil; D. M. Brommer; P. G. Dixon; M. E. Brown; K. Sherman-Morris (Natural Hazards, 2010)

Human immunodeficiency virus-1 evolutionary patterns associated with pathogenic processes in the brain - Susanna L Lamers; Marco Salemi; Derek C Galligan; Alanna Morris; Rebecca Gray; Gary Fogel; Li Zhao; Michael S McGrath (Journal of NeuroVirology, 2010)

Changes in plant form and function across altitudinal and wetness gradients in the wetlands of the Maloti-Drakensberg, South Africa - Erwin J. J. Sieben; Craig D. Morris; Donovan C. Kotze; A. Muthama Muasya (Plant Ecology, 2010)

Measuring mucus thickness in reef corals using a technique devised for vertebrate applications - Amita A. Jatkar; Barbara E. Brown; John C. Bythell; Reia Guppy; Nicholas J. Morris; Jeffery P. Pearson (Marine Biology, 2010)

Factors related to survival and treatment success in invasive candidiasis or candidemia: a pooled analysis of two large, prospective, micafungin trials - D. L. Horn; L. Ostrosky-Zeichner; M. I. Morris; A. J. Ullmann; C. Wu; D. N. Buell; L. L. Kovanda; O. A. Cornely (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Fluorescent Biosensors of Intracellular Targets from Genetically Encoded Reporters to Modular Polypeptide Probes - May C. Morris (Cell Biochemistry and Biophysics, 2010)

Structural and functional connectivity of marine fishes within a semi‐enclosed Newfoundland fjord - I. R. Bradbury; P. V. R. Snelgrove; P. Bentzen; B. De Young; R. S. Gregory; C. J. Morris (Journal of Fish Biology, 2009)
The interplay between structural connectivity ( i.e. habitat continuity) and functional connectivity ( i.e. dispersal probability) in marine fishes was examined in a coastal fjord (Holyrood Pond, Newfoundland, Canada) that is completely isolated from the North Atlantic Ocean for most of the year. Genetic differentiation was described in three species (rainbow smelt Osmerus mordax , white hake Urophycis tenuis and Atlantic cod Gadus morhua ) with contrasting life histories using seven to 10 microsatellite loci and a protein‐coding locus, Pan I ( G. morhua ). Analysis of microsatellite differentiation indicated clear genetic differences between the fjord and coastal regions; however, the magnitude of difference was no more elevated than adjacent bays and was not enhanced by the fjord's isolation. Osmerus mordax was characterized by the highest structure overall with moderate differentiation between the fjord and St Mary's Bay ( F ST c. 0·047). In contrast, U. tenuis and G. morhua displayed weak differentiation ( F ST Pan I locus in G. morhua between the fjord and other coastal locations. Interestingly, locus‐specific genetic differentiation and expected heterozygosity were negatively associated in O. mordax , in contrast to the positive associations observed in U. tenuis and G. morhua . Gene flow in these species is apparently unencumbered by limited structural connectivity, yet the observed differentiation suggests that population structuring exists over small scales despite high dispersal potential.

Lung-to-lung circulation times during exercise in heart failure - Norman R. Morris; Eric M. Snyder; Kenneth C. Beck; Bruce D. Johnson (European Journal of Applied Physiology, 2009)

Penetration of ultraviolet radiation in streams of eastern Pennsylvania: Topographic controls and the role of suspended particulates - Patrick Belmont; Donald P. Morris; Frank J. Pazzaglia; Stephen C. Peters (Aquatic Sciences, 2009)

Cloning and phylogenetic analysis of polyphenol oxidase genes in common wheat and related species - X. Y. He; Z. H. He; C. F. Morris; X. C. Xia (Genetic Resources and Crop Evolution, 2009)

Characterization of an animal model of aggressive metastatic pheochromocytoma linked to a specific gene signature - Lucia Martiniova; Edwin W. Lai; Abdel G. Elkahloun; Mones Abu-Asab; Andrea Wickremasinghe; Daniel C. Solis; Shiromi M. Perera; Thanh-Truc Huynh; Irina A. Lubensky; Arthur S. Tischler; Richard Kvetnansky; Salvatore Alesci; et al. (Clinical & Experimental Metastasis, 2009)

Biological Response Signature of Oil Brine Threats, Sediment Contaminants, and Crayfish Assemblages in an Indiana Watershed, USA - Thomas P. Simon; Charles C. Morris (Archives of Environmental Contamination and Toxicology, 2009)

Date mussel harvesting favours some blennioids - V. Parravicini; M. Donato; C. Morri; E. Villa; C. N. Bianchi (Journal of Fish Biology, 2008)
The consequences of date mussel Lithophaga lithophaga harvesting (DMH) on blennioid assemblages was evaluated at Capo Noli‐Bergeggi (Savona, north‐western Mediterranean Sea) in summer 2005, under the hypothesis that holes bored by L. lithophaga , and left empty by the collection of the bivalve, may represent refuges for these cryptobenthic fishes. Blenniidae and Tripterygiidae were identified to species, and their individuals counted together with the number of empty L. lithophaga holes. The results were compared between ‘impact’ sites affected by the destructive DMH and control sites using two‐way ANOVA, and showed that extensive removal of the boring mussels, dramatically increasing the availability of empty holes, favours total number of observed blennioid species and especially Parablennius zvonimiri abundance.

Individual Variation in 3-Methylbutanal: A Putative Link between Human Leukocyte Antigen and Skin Microflora - Sergey U. Savelev; Sanjay Antony-Babu; S. Craig Roberts; Huitu Wang; Anthony S. Clare; L. Morris Gosling; Marion Petrie; Michael Goodfellow; Anthony G. O’Donnell; Alan C. Ward (Journal of Chemical Ecology, 2008)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Molecular barley breeding - S. J. Rae; M. Macaulay; L. Ramsay; F. Leigh; D. Matthews; D. M. O’Sullivan; P. Donini; P. C. Morris; W. Powell; D. F. Marshall; R. Waugh; W. T. B. Thomas (Euphytica, 2007)

Tidal nitrogen exchanges across a freshwater wetland succession gradient in the upper Cooper River, South Carolina - H. N. McKellar; D. L. Tufford; M. C. Alford; P. Saroprayogi; B. J. Kelley; J. T. Morris (Estuaries and Coasts, 2007)

The role of the siderophore pyridine-2,6-bis (thiocarboxylic acid) (PDTC) in zinc utilization by Pseudomonas putida DSM 3601 - Lynne H. Leach; James C. Morris; Thomas A. Lewis (BioMetals, 2007)

Endosomal location of dopamine receptors in neuronal cell cytoplasm - Elizabeth C. Wolstencroft; Goran Simic; Nguyen thi Man; Ian Holt; Le Thanh Lam; Paul R. Buckland; Glenn E. Morris (Journal of Molecular Histology, 2007)

Rehabilitation of Swamp Paperbark (Melaleuca ericifolia) wetlands in south-eastern Australia: effects of hydrology, microtopography, plant age and planting technique on the success of community-based revegetation trials - Elisa J. Raulings; Paul I. Boon; Paul C. Bailey; Michael C. Roache; Kay Morris; Randall Robinson (Wetlands Ecology and Management, 2007)

Allelic variation of polyphenol oxidase (PPO) genes located on chromosomes 2A and 2D and development of functional markers for the PPO genes in common wheat - X. Y. He; Z. H. He; L. P. Zhang; D. J. Sun; C. F. Morris; E. P. Fuerst; X. C. Xia (Theoretical and Applied Genetics, 2007)

Managing Forest Structure and Fire Hazard—A Tool for Planners - Morris C. Johnson; David L. Peterson; Crystal L. Raymond (Journal of Forestry, 2007)
Fire planners and other resource managers need to examine a range of potential fuel and vegetation treatments to select options that will lead to desired outcomes for fire hazard and natural resource conditions. A new approach to this issue integrates concepts and tools from silviculture and fuel science to quantify outcomes for a large number of treatment options in dry forest stands in the western United States. Five silvicultural options (thinning from below to 50 trees per acre [tpa]; 100, 200, and 300 tpa; or no thinning) are considered in combination with three surface fuel treatments (pile and burn, prescribed fire, or no treatment), resulting in a range of alternative treatments for each representative stand. The Fire and Fuels Extension of the Forest Vegetation Simulator (FFE-FVS) was used to calculate (1) immediate effects of treatments on surface fuels, fire hazard, potential fire behavior, and forest structure (including visualizations); and (2) a 50-year time series of treatment effects at 10-year increments. These fuel treatment scenarios can be used as a starting point for examining alternatives for National Environmental Policy Act documents and other applications that require scientifically based information to quantify the effects of modifying forest structure and surface fuels. Forest managers also can develop customized treatments for specific locations and resource objectives. Scenarios and output can be used to inform ecological, economic, and sociological evaluations of the effects of fuel and vegetation treatments.

Fatty acid synthase effects on bovine adipose fat and milk fat - Chris A. Morris; Neil G. Cullen; Belinda C. Glass; Dianne L. Hyndman; Tim R. Manley; Sharon M. Hickey; John C. McEwan; Wayne S. Pitchford; Cynthia D.K. Bottema; Michael A.H. Lee (Mammalian Genome, 2007)

Enhanced Cd2+-selective root-tonoplast-transport in tobaccos expressing Arabidopsis cation exchangers - V. Koren’kov; S. Park; N.-H. Cheng; C. Sreevidya; J. Lachmansingh; J. Morris; K. Hirschi; G. J. Wagner (Planta, 2006)

Recovery and Characterization of a 30.7-kDa Protein from Bacillus licheniformis Associated with Inhibitory Activity Against Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococci, and Listeria monocytogenes - Mamdoh T. Jamal; Peter C. Morris; Rasmus Hansen; Derek J. Jamieson; J. Grant Burgess; Brian Austin (Marine Biotechnology, 2006)

Sensitivity of the population growth rate to demographic variability within and between phases of the disturbance cycle - W. F. Morris; S. Tuljapurkar; C. V. Haridas; E. S. Menges; C. C. Horvitz; C. A. Pfister (Ecology Letters, 2006)
For species in disturbance‐prone ecosystems, vital rates (survival, growth and reproduction) often vary both between and within phases of the cycle of disturbance and recovery; some of this variation is imposed by the environment, but some may represent adaptation of the life history to disturbance. Anthropogenic changes may amplify or impede these patterns of variation, and may have positive or negative effects on population growth. Using stochastic population projection matrix models, we develop stochastic elasticities (proportional derivatives of the long‐run population growth rate) to gauge the population effects of three types of change in demographic variability (changes in within‐ and between‐disturbance‐phase variability and phase‐specific changes). Computing these elasticities for five species of disturbance‐influenced perennial plants, we pinpoint demographic rates that may reveal adaptation to disturbance, and we demonstrate that species may differ in their responses to different types of changes in demographic variability driven by climate change.

Effects of plant harvesting and nutrient enrichment on phytoplankton community structure in a shallow urban lake - Kay Morris; Paul C. E. Bailey; Paul I. Boon; Leesa Hughes (Hydrobiologia, 2006)

Assessing the impact of modern recharge on a sandstone aquifer beneath a suburb of Doncaster, UK - Brian L. Morris; W. George Darling; Aidan A. Cronin; Joerg Rueedi; Emily J. Whitehead; Daren C. Gooddy (Hydrogeology Journal, 2006)

Influence of Dissolved Organic Matter on Acute Toxicity of Zinc to Larval Fathead Minnows (Pimephales promelas) - Robert B. Bringolf; Brady A. Morris; Connie J. Boese; Robert C. Santore; Herbert E. Allen; Joseph S. Meyer (Archives of Environmental Contamination and Toxicology, 2006)

Relationship of intertidal surface sediment chlorophyll concentration to hyperspectral reflectance and chlorophyll fluorescence - Jacco C. Kromkamp; Edward P. Morris; Rodney M. Forster; Claire Honeywill; Scott Hagerthey; David M. Paterson (Estuaries and Coasts, 2006)

The Effect of Physician Permission Versus Notification on Research Recruitment through Cancer Registries (United States) - Laura M. Beskow; Robert C. Millikan; Robert S. Sandler; Paul A. Godley; Bryan J. Weiner; Morris Weinberger (Cancer Causes & Control, 2006)

A Local-Scale In Situ Approach for Stressor Identification of Biologically Impaired Aquatic Systems - C. C. Morris; T. P. Simon; S. A. Newhouse (Archives of Environmental Contamination and Toxicology, 2006)

From “Snakebites in the new millennium: A state-of-the-art symposium” - J. Audi; S. A. Seifert; J. F. Gennaro; J. W. Skimming; L. H. S. Van Mierop; C. S. Kitchens; M. D. Cardwell; S. P. Bush; R. T. Clark; E. A. Dugan; R. C. Dart; S. R. Rose; et al. (Journal of Medical Toxicology, 2006)

Molecular and biochemical characterization of puroindoline a and b alleles in Chinese landraces and historical cultivars - F. Chen; Z. H. He; X. C. Xia; L. Q. Xia; X. Y. Zhang; M. Lillemo; C. F. Morris (Theoretical and Applied Genetics, 2006)

Identification of a tandem duplicated array in the Rhox α locus on mouse chromosome X - Lucy Morris; Julie Gordon; C. Clare Blackburn (Mammalian Genome, 2006)

Assessing the extent of induced leakage to an urban aquifer using environmental tracers: an example from Bishkek, capital of Kyrgyzstan, Central Asia - Brian L. Morris; W. George Darling; Daren C. Gooddy; Rafael G. Litvak; Ilka Neumann; Ekaterina J. Nemaltseva; Inna Poddubnaia (Hydrogeology Journal, 2006)

Patient Perspectives on Research Recruitment Through Cancer Registries - Laura M. Beskow; Robert S. Sandler; Robert C. Millikan; Morris Weinberger (Cancer Causes & Control, 2005)

Behavioural and pharmacological magnetic resonance imaging assessment of the effects of methylphenidate in a potential new rat model of attention deficit hyperactivity disorder - Katherine N. Hewitt; Yasmene B. Shah; Malcolm J. W. Prior; Peter G. Morris; Chris P. Hollis; Kevin C. F. Fone; Charles A. Marsden (Psychopharmacology, 2005)

Methodological considerations in rat brain BOLD contrast pharmacological MRI - C. A. Steward; C. A. Marsden; M. J. W. Prior; P. G. Morris; Y. B. Shah (Psychopharmacology, 2005)

Functional magnetic resonance imaging studies of opioid receptor-mediated modulation of noxious-evoked BOLD contrast in rats - Y. B. Shah; L. Haynes; M. J. W. Prior; C. A. Marsden; P. G. Morris; V. Chapman (Psychopharmacology, 2005)

The morphology of Tetracapsuloides bryosalmonae (Myxozoa: Malacosporea) spores released from Fredericella sultana (Bryozoa: Phylactolaemata) - C McGurk; D J Morris; J E Bron; A Adams (Journal of Fish Diseases, 2005)

Threshold levels of ERK activation for chemotactic migration differ for NGF and EGF in rat pheochromocytoma PC12 cells - W.-C. Ho; S. Uniyal; H. Zhou; V. L. Morris; B. M. C. Chan (Molecular and Cellular Biochemistry, 2005)

Functional analysis of a mutant form of the receptor tyrosine kinase Tie2 causing venous malformations - Paul N. Morris; Benjamin J. Dunmore; Amir Tadros; Douglas A. Marchuk; Diane C. Darland; Patricia A. D’Amore; Nicholas P. J. Brindle (Journal of Molecular Medicine, 2005)

Passive protection to bovine rotavirus (BRV) infection induced by a BRV VP8* produced in plants using a TMV-based vector - D. M. Pérez Filgueira; M. Mozgovoj; A. Wigdorovitz; M. J. Dus Santos; V. Parreño; K. Trono; F. M. Fernandez; C. Carrillo; L. A. Babiuk; T. J. Morris; M. V. Borca (Archives of Virology, 2004)

Determination and evaluation of the sequence and textural effects of the puroindoline a and puroindoline b genes in a population of synthetic hexaploid wheat - K. R. Gedye; C. F. Morris; A. D. Bettge (Theoretical and Applied Genetics, 2004)

Quantitative and qualitative evaluation of selected wheat varieties released since 1903 to increasing atmospheric carbon dioxide: can yield sensitivity to carbon dioxide be a factor in wheat performance? - L. H. Ziska; C. F. Morris; E. W. Goins (Global Change Biology, 2004)
The sensitivity of yield and quality parameters to carbon dioxide concentration [CO 2 ] was determined for individual lines of hard‐red spring wheat released in 1903, 1921, 1965 and 1996. All cultivars were evaluated with respect to growth and vegetative characteristics, grain yield and nutritional quality in response to [CO 2 ] increases that corresponded roughly to the CO 2 concentrations at the beginning of the 20th century, the current [CO 2 ], and the future projected [CO 2 ] for the end of the 21st century, respectively. Leaf area ratio (cm 2 g −1 ) declined and net assimilation rate (g m 2 day −1 ) increased in response to increasing [CO 2 ] for all cultivars during early vegetative growth. By maturity, vegetative growth of all cultivars significantly increased with the increase in [CO 2 ]. Seed yield increased significantly as [CO 2 ] increased, with yield sensitivity to rising [CO 2 ] inversely proportional to the year of cultivar release. Greater [CO 2 ] yield sensitivity in older cultivars was associated with whole‐plant characteristics such as increased tillering and panicle formation. Grain and flour protein, however, declined significantly with increasing [CO 2 ] and with year of release for all cultivars, although absolute values were higher for the older cultivars. Overall, these data indicate that yield response at the whole‐plant level to recent and projected increases in [CO 2 ] has declined with the release of newer cultivars, as has protein content of grain and flour. However, if agronomic practice can be adapted to maximize individual plant performance, [CO 2 ] responsive characteristics of older cultivars could, potentially, be incorporated as factors in future wheat selection.

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)

Coral communities of the northwestern Gulf of Aden (Yemen): variation in framework building related to environmental factors and biotic conditions - F. Benzoni; C. N. Bianchi; C. Morri (Coral Reefs, 2003)

Translocation breakpoint in two unrelated Tourette syndrome cases, within a region previously linked to the disorder - Fiona C. Crawford; Ghania Ait-Ghezala; Mark Morris; Maxine J. Sutcliffe; Robert A. Hauser; Archie A. Silver; Michael J. Mullan (Human Genetics, 2003)

Glomalin, an arbuscular-mycorrhizal fungal soil protein, responds to land-use change - Matthias C. Rillig; Philip W. Ramsey; Sherri Morris; Eldor A. Paul (Plant and Soil, 2003)

Development of improved PCR to prevent false positives and false negatives in the detection of Tetracapsula bryosalmonae , the causative agent of proliferative kidney disease - D C Morris; D J Morris; A Adams (Journal of Fish Diseases, 2002)
Proliferative kidney disease (PKD) is an economically significant disease caused by the myxozoan parasite Tetracapsula bryosalmonae . Polymerase chain reaction (PCR) protocols using primers specific for the small subunit ribosomal RNA (18S rDNA) gene of the parasite enable detection, however, false positive and negative results can render detection inconclusive. In this study a decontamination protocol was developed, using hydroxylamine hydrochloride (H), to prevent false positives by blocking re‐amplification of carry‐over contaminants. A mimic molecule was also developed and used as a competitive internal standard coamplified with target DNA in PCRs, revealing both true and false negatives. The sensitivity of one new and two existing primer sets was assessed with all primers detecting DNA equivalent to at least eight parasite cells per gram of tissue. This improved PCR protocol canprovide more reliable testing for T. bryosalmonae .

Molecular evidence of release of Tetracapsula bryosalmonae , the causative organism of proliferative kidney disease from infected salmonids into the environment - D C Morris; D J Morris; A Adams (Journal of Fish Diseases, 2002)

Universal, robust, highly quantitative SNP allele frequency measurement in DNA pools - Nadine Norton; Nigel M. Williams; Hywel J. Williams; Gillian Spurlock; George Kirov; Derek W. Morris; Bastiaan Hoogendoorn; Michael J. Owen; Michael C. O'Donovan (Human Genetics, 2002)

Exploitation of the Herpes simplex virus translocating protein VP22 to carry influenza virus proteins into cells for studies of apoptosis: direct confirmation that neuraminidase induces apoptosis and indications that other proteins may have a role - S. J. Morris; H. Smith; C. Sweet (Archives of Virology, 2002)

Molecular characterization of wheat polyphenol oxidase (PPO) - T. Demeke; C. Morris (Theoretical and Applied Genetics, 2002)

Substantial linkage disequilibrium across the insulin-degrading enzyme locus but no association with late-onset Alzheimer's disease - Richard Abraham; Amanda Myers; Fabienne Wavrant-DeVrieze; Marian L. Hamshere; Hollie V. Thomas; Helen Marshall; Danielle Compton; Gillian Spurlock; Dragana Turic; Bastiaan Hoogendoorn; Jennifer M. Kwon; Ronald C. Petersen; et al. (Human Genetics, 2001)

The CFTR-mediated protein secretion defect: pharmacological correction - McPherson M.; Pereira M.; Russell D.; McNeilly C.; Morris R.; Stratford F.; Dormer R. (Pflügers Archiv - European Journal of Physiology, 2001)

Localisation of wild-type and ?F508-CFTR in nasal epithelial cells - Dormer R.; McNeilly C.; Morris M.; Pereira M.; Doull I.; Becq F.; Mettey Y.; J-M Vierfond; McPherson M. (Pflügers Archiv - European Journal of Physiology, 2001)

Occurrence and ecological implications of pyrophosphate in estuaries - P. V. Sundareshwar; J. T. Morris; P. J. Pellechia; H. J. Cohen; D. E. Porter; B. C. Jones (Limnology and Oceanography, 2001)
Loading of bioavailable phosphorus, traditionally measured as soluble reactive phosphorus (SRP), contributes to the eutrophication of aquatic ecosystems. However, polyphosphates are also bioavailable but escape detection by the standard method used for measuring SRP. 31 P nuclear magnetic resonance spectrometric analysis of sediment extracts and enzymatic assay of surface waters reveal heretofore unreported presence of pyrophosphate (Ppi) in coastal wetlands. We show that the accumulation of Ppi (the smallest chemical form of polyphosphate) in coastal wetlands is related to human impact and can occur in quantities that exceed that of SRP. We further demonstrate that Ppi is readily utilized by microbes in coastal wetland sediments in the presence of nitrogen and carbon and can serve as a reservoir of orthophosphate. Thus, Ppi accumulation in estuaries will subsidize the in situ biogeochemical phosphorus cycle. This has important ecological implications for trophic responses and estuarine productivity.

Molecular analysis of the fibrinogen gene cluster in 16 patients with congenital afibrinogenemia: novel truncating mutations in the FGA and FGG genes - M. Neerman-Arbez; P. de Moerloose; A. Honsberger; G. Parlier; B. Arnuti; C. Biron; J.-Y. Borg; S. Eber; E. Meili; K. Peter-Salonen; L. Ripoll; C. Vervel; et al. (Human Genetics, 2001)

Biomass, carbonate standing stock and production of the mediterranean coralCladocora caespitosa (L.) - Andrea Peirano; Carla Morri; C. Nike Bianchi; Riccardo Rodolfo-Metalpa (Facies, 2001)

Clinical Manifestations and Molecular Epidemiology of Late Recurrent Candidemia, and Implications for Management - C. J. Clancy; F. Barchiesi; L. Falconi DiFrancesco; A. J. Morris; D. R. Snydman; V. L. Yu; G. Scalise; M. H. Nguyen (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

A catastrophic mass‐mortality episode of gorgonians and other organisms in the Ligurian Sea (North‐western Mediterranean), summer 1999 - C. Cerrano; G. Bavestrello; C.N. Bianchi; R. Cattaneo‐vietti; S. Bava; C. Morganti; C. Morri; P. Picco; G. Sara; S. Schiaparelli; A. Siccardi; F. Sponga (Ecology Letters, 2000)
In the late summer of 1999, an extensive mortality of gorgonians and other epi‐benthic organisms was observed in the Ligurian Sea (Mediterranean Sea) from the Tuscan Archipelago to Marseille. Quantitative data from Tino Island and Portofino Promontory indicated that the proportion of affected gorgonians ranged from 60% to 100% in populations having a density of 9–27.8 colonies m −2 , suggesting that millions of sea fans died along the coast of Liguria. This mass mortality episode coincided with a sudden increase of sea water temperature down to more than 50 m depth. Laboratory analyses showed that the colonies stressed by high temperature also underwent extensive attack by microrganisms (protozoans and fungi), which are interpreted as opportunistic pathogens.

A leucine to proline mutation in puroindoline b is frequently present in hard wheats from Northern Europe - M. Lillemo; C. F. Morris (Theoretical and Applied Genetics, 2000)

First survey of sessile communities on subtidal rocks in an area with hydrothermal vents: Milos Island, Aegean Sea - Silvia Cocito; C. Nike Bianchi; Carla Morri; Andrea Peirano (Hydrobiologia, 2000)

Coral mortality in NW Mediterranean - Ricardo Rodolfo Metalpa; C. Nike Bianchi; Andrea Peirano; Carla Morri (Coral Reefs, 2000)

MDH1: an apple homeobox gene belonging to the BEL1 family - Yi-Hu Dong; Jia-Long Yao; Ross G. Atkinson; Joanna J. Putterill; Bret A. Morris; Richard C. Gardner (Plant Molecular Biology, 2000)

Amphetamine-induced activation of forebrain EEG is prevented by noradrenergic β-receptor blockade in the halothane-anesthetized rat - C. W. Berridge; M. F. Morris (Psychopharmacology, 2000)

Seven Hox gene sequences from the asterinid starfish Patiriella exigua (Echinodermata: Asteroidea) - S. C. Long; V. B. Morris; M. Byrne (Hydrobiologia, 2000)

The spectrin skeleton of newly-invaginated plasma membrane - T. L. Herring; P. Juranka; J. McNally; H. Lesiuk; C. E. Morris (Journal of Muscle Research and Cell Motility, 2000)

Biodiversity of marine sessile epifauna at an Aegean island subject to hydrothermal activity: Milos, eastern Mediterranean Sea - C. Morri; C. N. Bianchi; S. Cocito; A. Peirano; A. M. De Biase; S. Aliani; M. Pansini; M. Boyer; F. Ferdeghini; M. Pestarino; P. Dando (Marine Biology, 1999)

A testis-specific gene, TPTE , encodes a putative transmembrane tyrosine phosphatase and maps to the pericentromeric region of human chromosomes 21 and 13, and to chromosomes 15, 22, and Y - H. Chen; C. Rossier; M.A. Morris; H.S. Scott; A. Gos; A. Bairoch; S.E. Antonarakis (Human Genetics, 1999)

A testis-specific gene, TPTE, encodes a putative transmembrane tyrosine phosphatase and maps to the pericentromeric region of human chromosomes 21 and 13, and to chromosomes 15, 22, and Y - H. Chen; C. Rossier; M.A. Morris; H.S. Scott; A. Gos; A. Bairoch; S.E. Antonarakis (Human Genetics, 1999)

Establishing the presence of a body temperature rhythm in chimpanzees (Pan troglodytes) using a tympanic membrane thermometer - L. A. Fowler; W. D. Hopkins; H. E. Albers; R. D. Morris; C. W. Hyatt (Primates, 1999)

Peripheral frequency mis-match in the primitive ensiferan Cyphoderris monstrosa (Orthoptera: Haglidae) - A. C. Mason; G. K. Morris; R. R. Hoy (Journal of Comparative Physiology A, 1999)

Isolation and characterization of a human hepatic epithelial-like cell line (AKN-1) from a normal liver - Andreas K. Nussler; Gianna Vergani; Susanne M. Gollin; Kenneth Dorko; Susanne Gansauge; Sidney M. Morris; Antony J. Demetris; Minoru Nomoto; Hans G. Beger; Stephen C. Strom (In Vitro Cellular & Developmental Biology - Animal, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Analysis of cytochrome P450 and phase II conjugating enzyme expression in adult male rat hepatocytes - Julio C. Davila; Dale L. Morris (In Vitro Cellular & Developmental Biology - Animal, 1999)

The matrix metalloproteinase inhibitor batimastat inhibits angiogenesis in liver metastases of B16F1 melanoma cells - Stewart Wylie; Ian C. MacDonald; Hemanth J. Varghese; Eric E. Schmidt; Vincent L. Morris; Alan C. Groom; Ann F. Chambers (Clinical & Experimental Metastasis, 1999)

Inhibition of angiogenesis in liver metastases by carboxyamidotriazole (CAI) - Keith J. Luzzi; Hemanth J. Varghese; Ian C. MacDonald; Eric E. Schmidt; Elise C. Kohn; Vincent L. Morris; Kathryn E. Marshall; Ann F. Chambers; Alan C. Groom (Angiogenesis, 1998)

Modeling Controlled Burning and Trampling Reduction for Conservation of Hudsonia montana - Kevin Gross; John R. Lockwood Iii; Cecil C. Frost; William F. Morris (Conservation Biology, 1998)
Populations of mountain golden heather ( Hudsonia montana ), a threatened North Carolina shrub, are declining due to the suppression of natural fires and increased trampling by hikers and campers. Consequently, proposed management strategies have focused on conducting controlled burns and restricting human traffic. To help design an optimal management plan, we used demographic data from a 5‐year field study of H. montana —which included a controlled burn—to construct size‐based population projection matrices. Using these matrices, we projected the consequences of instituting controlled burns and hiking and camping restrictions separately and in tandem. We also determined the burn frequency that would maximize H. montana ’s population growth rate. Finally, we used a stochastic model to determine how environmental fluctuations could alter the efficacy of conservation measures. Our results suggest that, although neither burning nor trampling reduction alone can reverse H. montana ’s decline, a judicious combination of the two has an excellent chance of doing so. A burn frequency of once every 6–8 years should maximize H. montana ’s population growth, although the interburn interval could be increased to 12–16 years without significantly jeopardizing the success of the management plan. Our results show that, even with the limited data available, size‐based projection matrix models can be useful tools for identifying promising combinations of multiple management strategies for most threatened plants. Modelado de Incendios Controlados y Reducción de Pisoteo para la Conservación de Hudsonia montana Las poblaciones del brezo dorado de montaña ( Hudsonia montana ), un arbusto de Carolina del Norte amenazado, están disminuyendo debido a la eliminación de incendios naturales y al incremento del pisoteo por escaladores y personas acampando. Consecuentemente, las estrategias de manejo propuestas se han enfocado en la conducción de quemas controladas y la restricción del tráfico de humanos. Para ayudar a diseñar un plan de manejo óptimo, utilizamos datos demográficos de 5 años de estudio de H. montana (incluyendo quema controlada) para construir matrices de proyección poblacional. Utilizando estas matrices proyectamos las consecuencias de instituir la quema controlada y restricciones a escaladores y campamentos en forma separada y en conjunto. También observamos la frecuencia de quema controlada que podría maximizar las tasas de crecimiento poblacional de H. montana . Finalmente, utilizamos un modelo estocástico para determinar cómo podrían afectar las variaciones ambientales la eficacia de estas medidas de conservación. Nuestros resultados sugieren que ni la quema ni la restricción del pisoteo pueden revertir las disminuciones de H. montana por si solos, pero una combinación de las dos medidas tendría excelentes posibilidades de lograrlo. Una frecuencia de quema de una vez cada 6‐8 años debería maximizar el crecimiento poblacional de H. montana , aunque el período de interquemas podría incrementarse hasta 12–16 años sin comprometer significativamente el éxito de los planes de manejo. Nuestros resultados muestran que aún con una cantidad limitada de datos disponibles, los modelos de matrices de proyección pueden ser herramientas muy útiles para la identificación de combinaciones de estrategias de manejo múltiples prometedoras para la mayoría de las plantas amenazadas.

Modeling Controlled Burning and Trampling Reduction for Conservation of Hudsonia montana - Kevin Gross; John R. Lockwood Iii; Cecil C. Frost; William F. Morris (Conservation Biology, 1998)

Detection and quantitation of a sodium-dependent sulfate cotransporter (NaSi-1) by sandwich-type enzyme-linked immunosorbent assay - Kazuko Sagawa; Debra C. DuBois; Bing Han; Richard R. Almon; Jürg Biber; Heini Murer; M. E. Morris (Pflügers Archiv - European Journal of Physiology, 1998)

Studies on the Formation of Crystalline Bacterial Biofilms on Urethral Catheters - D. Stickler; N. Morris; M.-C. Moreno; N. Sabbuba (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Evaluation of numerical simulations of capillary barrier field tests - Carl E. Morris; John C. Stormont (Geotechnical and Geological Engineering, 1998)

Studies on the formation of crystalline bacterial biofilms on urethral catheters - D. Stickler; N. Morris; M. -C. Moreno; N. Sabbuba (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Preclinical Assessment of Anti-cancer Therapeutic Strategies using in vivo Videomicroscopy - Ann F. Chambers; Ian C. MacDonald; Eric E. Schmidt; Vincent L. Morris; Alan C. Groom (Cancer and Metastasis Reviews, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Protection by ebselen against cisplatin-induced nephrotoxicity: Antioxidant system - K. Husain; C. Morris; C. Whitworth; G.L. Trammell; L.P. Rybak; S.M. Somani (Molecular and Cellular Biochemistry, 1998)

Cloning and characterisation of MEK1, an Arabidopsis gene encoding a homologue of MAP kinase kinase - Peter C. Morris; Danièle Guerrier; Jeff Leung; Jérôme Giraudat (Plant Molecular Biology, 1997)

Conformations of a synthetic peptide which facilitates the cellular delivery of nucleic acids - Pierre Vidal; May C. Morris; Laurent Chaloin; Jean Méry; Frédéric Heitz; Gilles Divita (International Journal of Peptide Research and Therapeutics, 1997)

A glycine to serine change in puroindoline b is associated with wheat grain hardness and low levels of starch-surface friabilin - M. J. Giroux; C. F. Morris (Theoretical and Applied Genetics, 1997)

British Inflammation Research Association Meeting: Is there any point in developing an anti-RA drug? National Heart and Lung Institute, London, UK, 21–22 November 1996 - F. Clay; C. Morris (Inflammation Research, 1997)

Rapid increases in cytokinin concentration in lateral buds of chickpea ( Cicer arietinum L.) during release of apical dominance - Colin G. N. Turnbull; Myriam A. A. Raymond; Ian C. Dodd; Suzanne E. Morris (Planta, 1997)

Spectroscopic characterization of quinone-site mutants of the bacterial photosynthetic reaction center - Philip D. Laible; Yuenian Zhang; Andrea L. Morris; Seth W. Snyder; Clint Ainsworth; Scott R. Greenfield; Michael R. Wasielewski; Pierre Parot; Barbara Schoepp; Marianne Schiffer; Deborah K. Hanson; Marion C. Thurnauer (Photosynthesis Research, 1997)

Phylogeny and Evolution of Selected Primates as Determined by Sequences of the ε-Globin Locus and 5′ Flanking Regions - Calvin A. Porter; Scott L. Page; John Czelusniak; Horacio Schneider; Maria Paula C. Schneider; Iracilda Sampaio; Morris Goodman (International Journal of Primatology, 1997)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)

Butyricin 7423 and the membrane H+-ATPase of Clostridium pasteurianum - D. J. Clarke; D. B. Kell; C. D. Morley; J. G. Morris (Archives of Microbiology, 1982)

Regulation of bacteriorhodopsin synthesis by growth rate in continuous cultures of Halobacterium halobium - P. J. Rogers; C. A. Morris (Archives of Microbiology, 1978)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Simian virus 40-Chinese hamster kidney cell interaction - Ch. Lavialle; J. Stvenet; A. G. Morris; H. G. Suarez; S. Estrade; J. -C. Salomon; R. Cassingena (Archives of Virology, 1975)

Detection of the ergosterol and episterol isomers lichesterol and fecosterol in nystatin-resistant mutants of Neurospora crassa - D. C. Morris; S. Safe; R. E. Subden (Biochemical Genetics, 1974)

A method developed for the study of yeast production withTorulopsis Utilis - A. C. Thaysen; Muriel Morris (Antonie van Leeuwenhoek, 1947)